Method for producing water-absorbing resin
Patent Information
- Application Number
- JP2023137023
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-25
- Publication Date
- 2025-03-07
AI Technical Summary
【0010】 本発明によれば、使用済み吸収性物品に含まれる吸水性樹脂、吸水性樹脂製造工程中の廃棄吸水性樹脂などの本来廃棄すべき吸水性樹脂を使用した場合に、吸水性能(特に加圧下吸収倍率)を改善し、また、吸水性能が安定化した吸水性樹脂を製造することができる。
Smart Images

Figure 2025031057000003 
Figure 2025031057000004 
Figure 2025031057000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a water-absorbent resin, which uses a solubilized polymer of a recovered water-absorbent resin as part of a raw material. [Background technology]
[0002] In recent years, water-absorbent resins have been widely used as water-absorbing agents in absorbent articles such as paper diapers, sanitary napkins, and incontinence pads, from the viewpoint of absorbing body fluids. Examples of such water-absorbent resins include hydrolyzates of starch-acrylonitrile graft copolymers, neutralized products of starch-acrylic acid graft polymers, saponified products of vinyl acetate-acrylic acid ester copolymers, and crosslinked products of partially neutralized acrylic acid polymers. From the viewpoint of water-absorbing performance, polyacrylic acid (salt)-based water-absorbent resins using acrylic acid and / or its salt as a monomer are most widely produced industrially.
[0003] Although absorbent articles are generally disposable, interest in recycling sanitary materials is growing due to the rise in environmental awareness. As a technology for recycling water-absorbing resins used in absorbent articles, there is a method of separating the water-absorbing resin from used absorbent articles and recycling the extracted water-absorbing resin. For example, Patent Document 1 discloses a method for recycling water-absorbing resins, in which the water-absorbing resin is separated from used absorbent articles and the extracted water-absorbing resin is subjected to washing and dehydration treatment. In addition to the method of recycling the water-absorbing resin as it is, a method has been developed in which the water-absorbing resin is decomposed and solubilized to separate it from other components in the paper diaper, and then the solubilized polymer is added to the manufacturing process of the water-absorbing resin to reuse it (Patent Documents 2 and 3). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2003-326161 A [Patent Document 2] International Publication No. 2020 / 213298 [Patent Document 3] International Publication No. 2022 / 080342 Summary of the Invention [Problem to be solved by the invention]
[0005] The amount of the solubilized polymer to be reused is much larger than that of the conventional additives added to the water absorbent resin, and it is difficult to mix the solubilized polymer uniformly with the materials in the manufacturing process in the recycling process compared to the conventional additives. In addition, if the mixing time is extended in order to mix the solubilized polymer uniformly, it leads to a decrease in productivity. On the other hand, if the solubilized polymer is not mixed uniformly, it leads to fluctuations in the physical properties (e.g., absorption capacity under no load) of the finally obtained water absorbent resin.
[0006] Furthermore, the performance (for example, absorbency against load (AAP)) of the water-absorbent resin obtained by recycling the solubilized polymer of the water-absorbent resin by the above-mentioned technique is not sufficient, and further improvement is required.
[0007] The object of the present invention is to provide a method for producing a water-absorbent resin using a solubilized polymer as a raw material in the production process of the water-absorbent resin, in which the solubilized polymer is mixed uniformly with the water-absorbent resin during the production process, and the physical properties of the resulting water-absorbent resin are stabilized. Another object of the present invention is to provide a method for producing a water-absorbent resin using a solubilized polymer as a raw material in the production process of the water-absorbent resin, in which the performance (particularly, the absorption capacity under pressure (AAP)) of the resulting water-absorbent resin is improved. [Means for solving the problem]
[0008] The present inventors have conducted intensive research to solve the above problems, and as a result, have found that the above problems can be solved by mixing the solubilized polymer in a heated state in any one of the production steps when producing a water absorbent resin using a solubilized polymer obtained by decomposing a recovered water absorbent resin such as a water absorbent resin contained in a used absorbent article or a waste water absorbent resin during a water absorbent resin production process as a part of a raw material, and thus completing the present invention.
[0009] That is, the above-mentioned object can be achieved by a method for producing a water-absorbent resin, which comprises a polymerization step of polymerizing an unsaturated monomer-containing aqueous solution to obtain a hydrous gel-like cross-linked polymer, and a drying step of drying the hydrous gel-like cross-linked polymer, and uses a solubilized polymer of a recovered water-absorbent resin as a part of a raw material, and in which the solubilized polymer is mixed in a heated state in any one of the production steps. Effect of the Invention
[0010] According to the present invention, when a water absorbent resin that should be discarded, such as a water absorbent resin contained in a used absorbent article or a water absorbent resin discarded during a water absorbent resin manufacturing process, is used, the water absorbent resin can be manufactured with improved water absorption performance (particularly, absorbency against pressure) and stabilized water absorption performance. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a schematic diagram showing a part of a production process for a water-absorbent resin according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic diagram showing a part of a production process for a water-absorbent resin according to another embodiment of the present invention. [Diagram 3] FIG. 3 is an enlarged schematic diagram of a portion of the Venturi tube. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The present invention will be described in detail below, but the scope of the present invention is not limited to these descriptions, and can be modified and implemented as appropriate within the scope of the present invention, other than the following examples. In addition, the embodiments described in this specification can be combined in any way to form other embodiments. Other embodiments obtained by appropriately combining the technical means disclosed in each of the embodiments are also included in the technical scope of the present invention. Throughout this specification, singular expressions should be understood to include the concept of the plural, unless otherwise specified. Therefore, singular articles (for example, in the case of English, "a", "an", "the", etc.) should be understood to include the concept of the plural, unless otherwise specified.
[0013] As used herein, the term "(meth)acrylic" includes both acrylic and methacrylic. Thus, for example, the term "(meth)acrylic acid" includes both acrylic acid and methacrylic acid. As used herein, "acid (salt)" means "acid and / or its salt."
[0014] [1] Definitions of terms [1-1] Water-absorbing resin The "water-absorbent resin" produced by the method of the present invention is a water-swellable, water-insoluble polymer gelling agent, and refers to a conventional water-absorbent resin having an absorption capacity of 10 to 1000 times, although it is not particularly limited thereto. More specifically, the water-absorbent resin before absorbing the liquid to be absorbed preferably satisfies the physical property of CRC of 5 g / g or more as "water-swellability".
[0015] The water-absorbing resin may be a polymer derived from a carboxyl group-containing unsaturated monomer. The water-absorbing resin may include a polymer having a partially neutralized carboxyl group. Specific examples of the water-absorbing resin include poly(meth)acrylic acid (salt)-based resins, polysulfonic acid (salt)-based resins, maleic anhydride (salt)-based resins, polyacrylamide-based resins, polyvinyl alcohol-based resins, polyethylene oxide-based resins, polyaspartic acid (salt)-based resins, polyglutamic acid (salt)-based resins, polyalginic acid (salt)-based resins, starch-based resins, and cellulose-based resins.
[0016] In this specification, the water-absorbing resin is not limited to an embodiment in which the total amount (100 mass %) is the water-absorbing resin alone, but may be a water-absorbing resin composition containing additives and the like.
[0017] [1-2] "Poly(meth)acrylic acid (salt)" The term "poly(meth)acrylic acid (salt)" in the present invention refers to a (co)polymer of (meth)acrylic acid and / or a salt thereof, and means a crosslinked polymer containing a structure derived from (meth)acrylic acid and / or a salt thereof (hereinafter also referred to as "(meth)acrylic acid (salt)") as a main component as a repeating unit, and containing a structure derived from an internal crosslinking agent as an optional component.
[0018] The above "main component" means that the amount (content) of (meth)acrylic acid (salt) used is preferably 50 mol % or more and 100 mol % or less, more preferably 70 mol % or more and 100 mol % or less, still more preferably 90 mol % or more and 100 mol % or less, and particularly preferably substantially 100 mol %, based on the total monomers used in the polymerization (all monomers excluding the crosslinking agent).
[0019] [1-3] Recycled water-absorbent resin The "recovered water-absorbent resin" refers to a water-absorbent resin that should be discarded. Specifically, it includes a water-absorbent resin contained in a used absorbent article (for example, a water-absorbent resin that has absorbed body fluids such as urine and blood in a used absorbent article) and a water-absorbent resin discarded during a water-absorbent resin manufacturing process (for example, fine powder or non-standardized products of water-absorbent resin generated during a water-absorbent resin manufacturing process). In addition, it may include a water-absorbent resin contained in a discarded absorbent article before use (for example, a water-absorbent resin discarded during the manufacturing of an absorbent article even if it has not absorbed body fluids such as urine and blood).
[0020] Among these, it is preferable to use a water-absorbent resin recovered (removed and collected) from used absorbent articles from the viewpoint of environmental protection, etc. That is, in one embodiment of the present invention, the recovered water-absorbent resin is a water-absorbent resin contained in a used absorbent article.
[0021] Here, "used absorbent articles" refer to sanitary materials that have been used by consumers and absorbed body fluids such as urine and blood. Examples of sanitary materials include paper diapers, sanitary napkins, and adult incontinence products (incontinence pads). Products similar to sanitary materials include pet sheets and pet diapers, and in the present invention, these animal urine disposal products are also included in the above sanitary materials.
[0022] The recovered water-absorbent resin is not limited to an embodiment in which the total amount (100% by mass) is the water-absorbent resin alone, and may be a water-absorbent resin composition containing a fibrous substance, a nonwoven fabric, an adhesive, an additive, etc. In addition, when the recovered water-absorbent resin is a water-absorbent resin contained in a used absorbent article, the recovered water-absorbent resin may be in a state of a hydrous gel in which water such as urine water has been taken in. Thus, the recovered water-absorbent resin may contain a water-absorbent resin in a state of a hydrous gel.
[0023] The mass of the water-absorbing resin and the recovered water-absorbing resin is a value converted into solid content unless otherwise specified. For example, when the mass of the water-absorbing resin contained in the used paper diaper is unknown, the mass of the water-absorbing resin contained in the unused paper diaper and the general value of the absorption capacity of the water-absorbing resin in the used paper diaper are used for calculation, or the content of the water-absorbing resin (solid content equivalent value) relative to the total mass of the used paper diaper is assumed to be 3% by mass or more and 9% by mass or less, and the mass of the water-absorbing resin is measured. Although the actual content of the water-absorbing resin may vary greatly depending on the usage state of the used paper diaper, a person skilled in the art can adjust the decomposition conditions appropriately while checking the actual decomposition state.
[0024] In one embodiment of the present invention, the CRC (before moisture absorption) of the recovered water absorbent resin (used to produce the solubilized polymer) is 20 g / g or more, 25 g / g or more, 27 g / g or more, or 30 g / g or more. In one embodiment of the present invention, the CRC (before moisture absorption) of the recovered water absorbent resin (used to produce the solubilized polymer) is 70 g / g or less, 50 g / g or less, or 45 g / g or less. The CRC is measured by the method described in the following examples.
[0025] In one embodiment of the present invention, the AAP (0.3 psi) of the recovered water absorbent resin (used to produce the solubilized polymer) is 10 g / g or more, 15 g / g or more, 20 g / g or more, 22 g / g or more, 24 g / g or more, or 25 g / g or more. In one embodiment of the present invention, the AAP (0.3 psi) of the water absorbent resin (used to produce the solubilized polymer) is 50 g / g or less, 45 g / g or less, 40 g / g or less, 35 g / g or less, or 30 g / g or less. The AAP is measured by the method described in the following examples.
[0026] [1-4] Absorbent articles An "absorbent article" is an article used for absorbing water. More specifically, an "absorbent article" is an absorbent article comprising an absorbent body containing a water-absorbent resin and a fibrous material, a top sheet having liquid permeability, and a back sheet having liquid impermeability. The absorbent body is suitably manufactured by blending a water-absorbent resin with a fibrous material, or by sandwiching a water-absorbent resin between fibrous materials and molding the mixture into a film, a tube, a sheet, or the like. Examples of the fibrous material include hydrophilic fibers such as ground wood pulp, cotton linters, crosslinked cellulose fibers, rayon, cotton, wool, acetate, vinylon, and the like.
[0027] "Absorbent article" includes both unused and used absorbent articles.
[0028] [1-5] EDANA "EDANA" is an abbreviation for European Disposables and Nonwovens Associations. EDANA is a European standard (almost a global standard) for measuring the physical properties of water-absorbent resins. In the present invention, unless otherwise specified, the physical properties of water-absorbent resins are measured in accordance with the original EDANA (revised in 2002 / publicly known document).
[0029] [2] Solubilizing polymers In the present invention, in order to recycle recovered water absorbent resins such as used water absorbent resins and water absorbent resins discarded in the manufacturing process, a solubilizing polymer for the recovered water absorbent resin is mixed during the manufacturing process of the water absorbent resin. First, the solubilizing polymer for the recovered water absorbent resin will be described.
[0030] The "solubilized polymer" is a decomposition product (liquid) obtained by decomposing a water-swellable (i.e., insoluble in water) recovered water-absorbent resin and solubilizing it in water. The solubilized polymer may be one in which all of the polymer is solubilized in water, or one in which only a part of the polymer is not solubilized. If the polymer appears dissolved in water without any residual residue visible in the water (if the interface between the water-absorbent resin and water cannot be visually recognized in the water), the polymer is deemed to be solubilized in water. If some undissolved swollen matter remains but is reduced compared to before the solubilization treatment, the polymer is deemed to be partially solubilized and a solubilized polymer is generated. Therefore, even if some undissolved swollen matter remains in the aqueous polymer solution after solubilization (decomposition), the polymer is referred to as a solubilized polymer. The solubilized polymer may be used in the form of an aqueous solution of the decomposition product obtained as it is. Furthermore, the decomposition product obtained may be diluted by adding water or the like. In this embodiment, the heated solubilized polymer is preferably a solution (preferably an aqueous solution) of the heated solubilized polymer.
[0031] In one embodiment of the present invention, the mass average molecular weight of the solubilizing polymer is 30,000 or more and 1,000,000 or less, or 40,000 or more and 800,000 or less. If the mass average molecular weight is within the above range, the water-soluble content of the water-absorbent resin produced by using the solubilizing polymer as a part of the raw material can be further reduced, and the water absorption properties can be further improved. In addition, the viscosity of the decomposition product solution (e.g., aqueous solution) can be appropriately controlled, so that the handling property is excellent. The method for measuring the mass average molecular weight is as follows.
[0032] Molecular weight of solubilizing polymer: (Preparation of measurement samples) The sample is dissolved in the following solvent to obtain a solution with a concentration of 0.1% by mass. The resulting solution is then passed through a filter (GL Sciences: GL Chromatodisk, aqueous 25A, pore size 0.2 μm) to obtain the measurement sample. Solvent: Aqueous solution (pH 6.35 to 6.38) containing 60 mM sodium dihydrogen phosphate dihydrate, 20 mM disodium hydrogen phosphate dodecahydrate, and 400 ppm sodium azide. Using this measurement sample, perform GPC measurement under the following measurement conditions.
[0033] (GPC measurement conditions) The above-mentioned measurement sample was subjected to GPC measurement using a Viscotec TDAmax manufactured by Malvern Instruments. The measurement device is equipped with a size exclusion chromatograph, a refractive index detector, a light scattering detector and a capillary viscometer. The measurement device and measurement conditions are as follows. Pump, autosampler: Viscotec GPCmax (Malvern) Guard column: OHpak SB-G (Showa Denko Co., Ltd.) Column: OHpak SB-806MHQ (Showa Denko K.K.), two columns connected in series Detector: Viscotec TDAmax (Malvern) Solvent: Aqueous solution containing 60 mM sodium dihydrogen phosphate dihydrate, 20 mM sodium dihydrogen phosphate dodecahydrate, and 400 ppm sodium azide (pH 6.35 to 6.38). Flow rate: 0.5mL / min Injection volume: 100μL.
[0034] The water used in GPC measurement should be pure water from which impurities have been thoroughly removed. In addition, GPC measurement should be performed with a sufficient amount of solvent flowing through the measurement device, with the baseline of the detection value stable, and in particular, with no noise peaks in the light scattering detector.
[0035] The measurement device is calibrated using polyoxyethylene glycol [mass average molecular weight (Mw): 21966, molecular weight distribution (Mw / Mn): 1.0, differential refractive index (dn / dc): 0.132, solvent refractive index: 1.33] as a standard sample. The measurement is performed with the differential refractive index (dn / dc) of the decomposition product to be measured set to 0.12 and the solvent refractive index set to 1.33. Data collection and analysis of the refractive index, light scattering intensity, and viscosity are performed using Viscotek OmniSEC4.7.0 (registered trademark) software.
[0036] After the measurement, the data obtained from the refractive index (RI) and light scattering intensity (angle: 7°) (LALS), as well as the viscometer (DP) are used to calculate the mass average molecular weight (Mw), number average molecular weight (Mn), and molecular weight distribution (Mw / Mn) of the decomposition products.
[0037] The method for producing a solubilized polymer is not particularly limited, and known methods can be used. For example, a technique for solubilizing a water-absorbent resin by heating a water-absorbent resin or a mixture of a water-absorbent resin and pulp in the presence of an oxidizing agent such as hydrogen peroxide or a persulfate (e.g., JP-A-4-317785, JP-A-6-313008, JP-A-2003-321574), a technique for solubilizing a water-absorbent resin using ascorbic acid as a reducing agent under conditions of pH 4 to 7.5 (e.g., JP-A-05-247221), a technique for solubilizing a water-absorbent resin using a reducing agent and a transition metal ion (e.g., JP-A-2019-131789), and a technique for solubilizing a water-absorbent resin by heating in the presence of an oxidizing water-soluble salt (e.g., WO2021 / 0421 No. 13), as a technique for decomposing a superabsorbent resin and solubilizing it in water, for example, a technique for solubilizing a water-absorbent resin using ozone water (e.g., JP 2014-217835 A, JP 2017-100133 A), a technique for solubilizing a water-absorbent resin using a combination of an oxidizing agent and a transition metal ion such as an iron ion or a copper ion (e.g., JP 11-172039 A), a technique for oxidation treatment with hypochlorous acid (salt), hydrogen peroxide, persulfuric acid, chlorine or a water-soluble oxidizing and reducing agent (e.g., JP 2013-150977 A), and a technique for solubilizing a water-absorbent resin using an alkali compound (e.g., JP 2020-49398 A) can be used.
[0038] An embodiment for producing a solubilizing polymer is described below, but the present invention is not limited to the following.
[0039] The recovered water absorbent resin as the raw material is preferably a crosslinked polymer, and is preferably a crosslinked polymer having an acid group-containing unsaturated monomer and an internal crosslinking agent as constituent units, as described in the section on the method for producing a water absorbent resin below.
[0040] The recovered water absorbent resin and the decomposition agent as raw materials, and optionally water, are mixed. Here, the water is not particularly limited as long as it is clean, and examples thereof include tap water, industrial water, ion-exchanged water, and pure water. The mixing ratio of water and the recovered water absorbent resin as raw materials is not particularly limited, but the amount of water mixed is preferably 66 parts by mass or more and 1900 parts by mass or less, more preferably 80 parts by mass or more and 1500 parts by mass or less, and even more preferably 100 parts by mass or more and 900 parts by mass or less, relative to 100 parts by mass of the recovered water absorbent resin (solid content). If the amount of water mixed is 66 parts by mass or more, the recovered water absorbent resin flows and can be sufficiently decomposed. In addition, if the amount of water mixed is 1900 parts by mass or less, the obtained decomposition product is obtained at a sufficient concentration, so it can be used as it is or simply concentrated in the subsequent manufacturing process. If the recovered water absorbent resin as raw material is in the state of a hydrous gel, the moisture absorbed in the water absorbent resin may be used as it is.
[0041] The decomposing agent is not particularly limited as long as it can decompose the recovered water absorbent resin and solubilize it in water, and any decomposing agent may be used. Examples include oxidizing agents, ozone water, a combination of an oxidizing agent and a transition metal ion such as iron ion or copper ion, a combination of a reducing agent and a transition metal ion, and an alkali compound. When a decomposing agent (for example, an oxidizing agent, an iron ion, an alkali compound, etc.) is contained in the recovered water absorbent resin, these decomposing agents may be used as they are. Among these, since the decomposition efficiency is good, it is preferable that the decomposition treatment of the recovered water absorbent resin is performed by a decomposition treatment with an oxidizing agent. In addition, although the oxidizing agent has a high decomposition efficiency, it remains in the solubilized polymer, so that it may affect the physical properties of the obtained water absorbent resin. By heating the solubilized polymer, the oxidizing agent is easily decomposed, and the physical properties of the obtained water absorbent resin are easily improved. In other words, it is a preferable embodiment that the decomposition treatment of the recovered water absorbent resin is performed by a decomposition treatment with an oxidizing agent, in that the effect of the present invention is easily obtained when an oxidizing agent is used as a decomposing agent.
[0042] The oxidizing agent that can be used as the decomposition agent is a compound having oxidizing properties and generating radicals when heated. In addition, radicals are generated when used in combination with a reducing agent and / or a compound that generates transition metal ions.
[0043] Examples of such oxidizing agents include persulfates, such as sodium persulfate, potassium persulfate, and ammonium persulfate; peroxides, such as hydrogen peroxide, alkyl hydroperoxides, and peresters; perchlorates, such as sodium perchlorate and potassium perchlorate; periodates, such as sodium periodate and potassium periodate; percarbonates, perborates, and peracetic acid. The above-mentioned oxidizing agents may be used alone or in combination of two or more. Of these, hydrogen peroxide is preferably used.
[0044] In this embodiment, the amount of the oxidizing agent is preferably 0.1 parts by mass or more and 50 parts by mass or less, more preferably 0.3 parts by mass or more and 45 parts by mass or less, and even more preferably 0.5 parts by mass or more and 40 parts by mass or less, relative to 100 parts by mass (solid content) of the recovered water absorbent resin. With the above amount of the oxidizing agent, the recovered water absorbent resin can be efficiently decomposed, and coloring of the obtained solubilized polymer can be sufficiently prevented.
[0045] A reducing agent may be used as the decomposing agent. The reducing agent is a compound having reducing properties, and generates radicals when used in combination with the above-mentioned oxidizing agent or the below-mentioned compound that generates transition metal ions. Examples of the reducing agent include sulfurous acid (salt), hydrogen sulfite (salt), phosphorous acid (salt), hypophosphorous acid (salt), thiosulfuric acid (salt), formic acid, oxalic acid, erythorbic acid, amines, ascorbic acid (salt) or its derivatives (e.g., L-ascorbic acid (salt), isoascorbic acid (salt), and alkyl esters of ascorbic acid), phosphoric acid esters, and sulfate esters. The above reducing agents may be used alone or in combination of two or more. Among these, sulfurous acid (salt), hydrogen sulfite (salt), L-ascorbic acid (salt), and isoascorbic acid (salt) are preferably used. In this embodiment, the amount of the reducing agent is preferably 0.01 parts by mass or more and 50 parts by mass or less, more preferably 0.05 parts by mass or more and 25 parts by mass or less, and even more preferably 0.1 parts by mass or more and 5 parts by mass or less, relative to 100 parts by mass of the recovered water absorbent resin. With the above amount of the reducing agent, the recovered water absorbent resin can be efficiently decomposed, and coloration of the resulting decomposition product can be sufficiently prevented.
[0046] A transition metal ion may be used as the decomposition agent. The transition metal ion generates radicals by the Fenton reaction when used in combination with the above-mentioned oxidizing agent. Also, the transition metal ion generates radicals when used in combination with the above-mentioned reducing agent. Examples of the transition metal ion include Cu. 2+ , Ag + , Fe 2+ , Fe 3+ , Al 3+ , Ni 2+ , Mn 2+ The above transition metal ions may be used alone or in combination of two or more. Among these, iron ion (Fe 2+ ), copper ions (Cu 2+ ) is preferred, and iron ions (Fe 2+) is more preferable. Examples of the compound that generates the transition metal ions as described above include chlorides and hydrates thereof, such as ferrous chloride, organic acid salts and hydrates thereof, such as ferrous fumarate, ferrous oxalate, ferrous chloride, sodium ferrous citrate, ferrous gluconate, ferrous citrate, ferrous acetate, sulfates and hydrates thereof, such as ferrous sulfate, and the like. The above compounds may be used alone or in combination of two or more. In this embodiment, the amount of transition metal ions is 1×10 to 100 parts by mass of the recovered water absorbent resin. -6 It is preferably from 1 part by mass to 1 part by mass, and more preferably from 1×10 -5 The amount of the transition metal ion is preferably from 0.001 to 0.1 parts by mass, more preferably from 0.02 to 0.5 parts by mass, and even more preferably from 0.001 to 0.1 parts by mass. The amount of the transition metal ion in the above range can efficiently decompose the recovered water absorbent resin and can sufficiently prevent coloration of the solubilized polymer obtained.
[0047] An alkaline compound may be used as the decomposing agent. The alkaline compound is a compound that solubilizes the crosslinked portion of the water-absorbent resin by alkaline hydrolysis. Examples of such alkaline compounds include hydroxides of alkali metals such as lithium hydroxide, potassium hydroxide, and sodium hydroxide; hydroxides of alkaline earth metals such as magnesium hydroxide and calcium hydroxide; ammonia; and amine compounds such as aliphatic amines, alicyclic amines, and aromatic amines. The above alkaline compounds may be used alone or in combination of two or more kinds. Among these, hydroxides of alkali metals and hydroxides of alkaline earth metals are preferred.
[0048] The decomposition conditions are not particularly limited, but it is preferable to carry out the decomposition under appropriate pH conditions. Specifically, it is preferable to adjust the pH of the mixture containing the recovered water absorbent resin, water, and the decomposing agent to a range of 6.5 to 9.5 (more preferably 6.5 to 9.0, particularly preferably 6.5 to 8.5). If the pH is within the above range, the recovered water absorbent resin can be efficiently decomposed, and coloring of the solubilized polymer obtained can be sufficiently prevented. The pH of the mixture may be adjusted within the range for a certain period of time that allows the decomposition of the recovered water absorbent resin to proceed sufficiently. It is preferable to adjust the pH to fall within the above pH range from the start of decomposition to the end of decomposition. The pH of the mixture can be adjusted by adding a pH adjuster such as an acid or a base as necessary. Examples of the acid used include, but are not limited to, inorganic acids such as hydrochloric acid, sulfuric acid, nitric acid, and phosphoric acid, and organic acids such as acetic acid and citric acid. Examples of the base that can be used include, but are not limited to, sodium hydroxide, sodium carbonate, potassium hydroxide hydroxide, and magnesium hydroxide.
[0049] The temperature at which the recovered water absorbent resin is decomposed is preferably 50°C or higher and 130°C or lower, more preferably 65°C or higher and 120°C or lower, and even more preferably 80°C or higher and 110°C or lower. At the above temperatures, a sufficient amount of radicals is generated from the decomposing agent, and the decomposed product can be obtained in a short time. As a method for adjusting the decomposition temperature, the recovered water absorbent resin, the decomposing agent, and water may be mixed at room temperature (e.g., 20°C or higher and 25°C or lower), and then the temperature of the mixture may be adjusted to a predetermined value while stirring if necessary. Alternatively, the recovered water absorbent resin, the decomposing agent, and water may be mixed at room temperature (e.g., 20°C or higher and 25°C or lower), and then the recovered water absorbent resin, the decomposing agent, and water may be introduced into a container whose temperature has been adjusted to a predetermined temperature by a known means such as an oil bath, and then stirred.
[0050] After the decomposition reaction is completed, the decomposition agent may be removed by, for example, adding a basic substance such as sodium carbonate and stirring for a certain period of time.
[0051] The decomposition product obtained by the decomposition operation may be subjected to a dissolved oxygen removal treatment (replacement with an inert gas), but according to the present embodiment, it is not necessary to perform the dissolved oxygen removal treatment. In this embodiment, the stability of the physical properties of the water absorbent resin is ensured even without performing the dissolved oxygen removal treatment.
[0052] The decomposition product obtained by the decomposition operation may be used as it is (for recycling) as a raw material in the manufacturing process of the water absorbent resin, or the concentration may be appropriately adjusted by adding water, etc. The decomposition product or dilution product thus obtained becomes the solubilized polymer of the recovered water absorbent resin.
[0053] The concentration of the solubilized polymer used as a raw material in the manufacturing process of the water absorbent resin is preferably 5% by mass or more in terms of handling, more preferably 5% by mass or more to 40% by mass or less, even more preferably 8% by mass or more to 40% by mass or less, and even more preferably 8% by mass or more to 30% by mass or less. The aqueous solution referred to here also includes an aqueous dispersion (an aqueous solution or an aqueous dispersion). In addition, for the solubilized polymer in a heated state, from the viewpoint of handling, it is preferably 5% by mass or more in terms of handling, more preferably 5% by mass or more to 40% by mass or less, even more preferably 8% by mass or more to 40% by mass or less, and even more preferably 8% by mass or more to 30% by mass or less.
[0054] In order to prevent unexpected polymerization from proceeding, particularly when mixed with a monomer (aqueous solution), the solubilizing polymer may contain a polymerization inhibitor. The polymerization inhibitor is not particularly limited, but examples thereof include N-oxyl compounds, manganese compounds, and substituted phenol compounds disclosed in International Publication No. 2008 / 096713 (US Patent Application Publication No. 2010 / 0009846). Among them, substituted phenols are preferred, and methoxyphenols are particularly preferred.
[0055] Examples of the methoxyphenols include o-, m-, and p-methoxyphenols and methoxyphenols having one or more substituents such as a methyl group, a t-butyl group, and a hydroxyl group. In the present invention, p-methoxyphenol is particularly preferred.
[0056] The amount of the polymerization inhibitor in the solubilized polymer (solid content) is usually 1 ppm (by mass) or more and 250 ppm or less, preferably 10 ppm or more and 200 ppm or less.
[0057] The yellowness index (YI value) in the Hunter Lab color system in an aqueous solution state of 8% by mass or more and 10% by mass or less (hereinafter, simply referred to as the YI value) of the solubilized polymer is preferably 10 or less. By using such a solubilized polymer, coloration of the obtained water absorbent resin can be suppressed. The YI value is preferably 8 or less, more preferably 4 or less. The closer the yellowness index is to 0, the lower the coloration and the more substantially white the resin becomes. The YI value can be measured by adjusting the solubilized polymer to an aqueous solution having a solid content of 8% by mass or more and 10% by mass or less, and by the method described in the Examples. Examples of a method for controlling the yellowness of the solubilized polymer include the addition of a reducing agent or a bleaching agent.
[0058] The transition metal ion content in the solubilized polymer is preferably 10 ppm (by mass) or less (based on solid content). By using such a solubilized polymer, the physical properties (particularly the absorbency against pressure (AAP)) of the obtained water absorbent resin can be improved. The transition metal ions are as described above. The method for measuring the transition metal ions includes the method described in the following examples. The method for controlling the amount of transition metal ions in the solubilized polymer includes washing the water absorbent resin, which is the raw material of the solubilized polymer, with water, and adding a chelating agent that captures the transition metal ions.
[0059] The L-ascorbic acid in the solubilized polymer is preferably 10 ppm (by mass) or less (based on solid content). By using such a solubilized polymer, the physical properties (particularly the absorbency against pressure (AAP)) of the obtained water absorbent resin can be improved. The method for measuring L-ascorbic acid includes the method described in the following examples. The method for controlling the amount of L-ascorbic acid in the solubilized polymer includes the addition of an oxidizing agent.
[0060] The oxidizing agent in the solubilized polymer is preferably 100 (mass) ppm or less (relative to solid content). By using such a solubilized polymer, the physical properties (particularly the absorbency against pressure (AAP)) of the obtained water absorbent resin can be improved. The oxidizing agent is as described above. The method for measuring the oxidizing agent can be the method described in the following examples.
[0061] [3] Method for producing water-absorbent resin The method for producing a water-absorbent resin according to the present invention includes a polymerization step of polymerizing an unsaturated monomer-containing aqueous solution to obtain a hydrogel-like crosslinked polymer (hereinafter also simply referred to as a hydrogel), and a drying step of drying the hydrogel crosslinked polymer. Preferably, this production method further includes a cooling step, a pulverization step of the dried product, a classification step, a surface crosslinking step, or a granulation step after surface crosslinking. In addition, the method may include a preparation step of an unsaturated monomer-containing aqueous solution (hereinafter also simply referred to as a monomer aqueous solution), a step of adding various additives, a fine powder removal step and a fine powder recycling step (fine powder recovery step), or a filling step. Furthermore, various known steps may be included depending on the purpose.
[0062] The heated solubilized polymer is mixed in any of the processes for the water-absorbent resin, specifically, the process for preparing an unsaturated monomer aqueous solution, the polymerization process, the gel crushing process, the drying process, the surface cross-linking process, and the like.
[0063] In order to heat the solubilized polymer, the solubilized polymer obtained by the decomposition operation is heated. The heating method is not particularly limited, and various containers and stirring devices having a heating function are used, for example, a jacketed storage tank shown in FIG. 8 of WO 2012 / 102406, a storage tank equipped with a multi-tube heat exchanger outside the storage tank shown in FIG. 9 of the same publication, and various heating and stirring devices (for example, kneaders) are used. When stirring is performed using a stirring blade or the like, the stirring part may also be heated. When stirring is performed as necessary, the rotation speed and time are appropriately determined, for example, at 0.1 rpm or more and 5000 rpm or less, or further at 1 rpm or more and 1000 rpm or less, for 1 second or more and 10 hours or less. Furthermore, heating may be performed continuously or intermittently.
[0064] The heating temperature of the solubilized polymer is preferably 30°C or more and 100°C or less. That is, the solubilized polymer of the water absorbent resin in the heated state is heated to 30°C or more and 100°C or less. The solubilized polymer of the water absorbent resin in the heated state is preferably heated to 50°C or more and 100°C or less, more preferably heated to 55°C or more and 100°C or less, and even more preferably heated to 55°C or more and 80°C or less. By heating to a temperature equal to or higher than the above lower limit, the mixing uniformity of the solubilized polymer is further improved, and the increase in coloration and / or water-soluble content is suppressed. In addition, the physical properties (e.g., absorption capacity without load (CRC)) of the obtained water absorbent resin are stabilized. In addition, even when the recovered water absorbent resin is used in the manufacturing process of the water absorbent resin, the performance of the obtained water absorbent resin (particularly, absorption capacity under load (AAP)) can be maintained or improved. In addition, in the form in which the solubilized polymer is mixed with an unsaturated monomer, polymerization is stabilized. By setting the temperature to the above upper limit or less, it is possible to prevent the solubilized polymer from being excessively heated.
[0065] In addition, in view of the stability of physical properties and the improvement of the physical properties of the obtained water absorbent resin (particularly, the absorbency under pressure (AAP)), the heating temperature is preferably within a substantially constant temperature range, particularly the same temperature, and specifically, the temperature of the solubilized polymer in the heated state is preferably controlled within a range of ±10°C, ±9°C, ±6°C, ±3°C, or ±1°C. Here, the temperature of the solubilized polymer in the heated state being within ±10°C means that the temperature range of the solubilized polymer (the difference between the maximum temperature and the minimum temperature) is within 20°C. Similarly, within ±9°C, ±6°C, ±3°C, or ±1°C means that the temperature range of the solubilized polymer (the difference between the maximum temperature and the minimum temperature) is within 18°C, 12°C, 6°C, or 2°C.
[0066] The temperature difference between the solubilized polymer and the water absorbent resin raw material to be mixed is preferably 50°C or less (lower limit 0°C), more preferably 0°C or more to 30°C or less, and even more preferably 0°C or more to 20°C or less. By having the temperature difference between the solubilized polymer and the water absorbent resin raw material to be mixed within the above range, the mixing of the two is more likely to be uniform, and the physical properties of the resulting water absorbent resin (particularly, the absorption capacity under pressure (AAP)) can be improved. The temperatures of the solubilized polymer and the water absorbent resin raw material to be mixed may be controlled so as to achieve the above temperature difference. Here, the water absorbent resin raw material to be mixed with the solubilized polymer is preferably at least one selected from the group consisting of water for producing an unsaturated monomer aqueous solution, an unsaturated monomer-containing aqueous solution, and a hydrous gel.
[0067] The water-absorbent resin raw material to be mixed with the solubilized polymer may be in a heated state. Here, the water-absorbent resin raw material in a heated state is heated to 30° C. or more and 100° C. or less, preferably 40° C. or more and 100° C. or less, more preferably 40° C. or more and 80° C. or less. By heating in such a temperature range, the solubilized polymer and the water-absorbent resin raw material are easily mixed uniformly, and the performance of the obtained water-absorbent resin (particularly, the absorbency against pressure (AAP)) can be improved.
[0068] The heated solubilized polymer is preferably mixed in the manufacturing process before the drying process. Specifically, the heated solubilized polymer is preferably mixed with an unsaturated monomer (form 1) and / or mixed with a hydrogel crosslinked polymer (form 2), and the heated solubilized polymer is more preferably mixed with an unsaturated monomer (form 1). By mixing the solubilized polymer with the unsaturated monomer and / or the hydrogel crosslinked polymer before the drying process, the solubilized polymer (liquid) is easily mixed uniformly during the manufacturing process.
[0069] Form 1: Unsaturated monomer and heated solubilized polymer are mixed The form (form 1) in which the unsaturated monomer and the heated solubilized polymer are mixed is preferably a form in which the unsaturated monomer-containing aqueous solution before polymerization contains the solubilized polymer. According to form 1, the mixing uniformity of the solubilized polymer during the production process is further improved, and the performance of the obtained water absorbent resin (especially, the absorbency against pressure (AAP)) is improved, which is preferable.
[0070] In addition, when a solubilizing polymer is added to an aqueous monomer solution, the amount of the solubilizing polymer is usually much larger than that of other additives, which tends to cause delay in polymerization of the monomer and increase in the fluctuation of the induction time (polymerization start time). By adding a heated solubilizing polymer, it is possible to suppress the polymerization delay and the fluctuation of the induction time (polymerization start time). Note that suppression of polymerization delay includes shortening the induction time (polymerization start time) as described in the examples below.
[0071] Specific examples of Form 1 include a form in which a heated solubilized polymer is added during the production process in the "process for preparing an aqueous monomer solution" (Form 1-1) and / or the "polymerization process" (Form 1-2).
[0072] In the embodiment 1-1, specifically, an unsaturated monomer, water, an internal crosslinking agent, other additives, and a solubilizing polymer are mixed to prepare an unsaturated monomer-containing aqueous solution. The order of addition of each component is not particularly important. For example, an unsaturated monomer, water, an internal crosslinking agent, other additives, and a solubilizing polymer may be added and mixed at once, or an aqueous solution containing a monomer, water, an internal crosslinking agent, and other additives may be prepared, and then a solubilizing polymer may be mixed.
[0073] The amount of the solubilizing polymer added (solid content) is preferably 1 mass % or more and 60 mass % or less (solid content) relative to the total amount of unsaturated monomers (excluding the internal crosslinking agent) when producing the water absorbent resin, more preferably 5 mass % or more and less than 50 mass %, and even more preferably more than 5 mass % and less than 40 mass %.
[0074] In the embodiment 1, after mixing the unsaturated monomer and the heated solubilized polymer, the time from adding the polymerization initiator to the initiation of polymerization is preferably within 5 minutes, more preferably within 3 minutes. By shortening the time until the initiation of polymerization, the performance of the obtained water absorbent resin (particularly, the absorbency against pressure (AAP)) can be improved.
[0075] Hereinafter, the first embodiment will be described with reference to the drawings.
[0076] Fig. 1 is a schematic diagram showing a part of a manufacturing process of a water-absorbent resin according to one embodiment of the present invention. In the following description of the drawings, the same elements are given the same reference numerals, and duplicated description will be omitted. The dimensional ratios in the drawings are exaggerated for convenience of explanation, and may differ from the actual ratios. In addition, although a plurality of valves for adjusting the flow rate and pressure are provided in the piping system, illustration of these valves is omitted in Figs. 1 and 2.
[0077] As shown in FIG. 1, the manufacturing process of the water absorbent resin includes a solubilization reaction tank 10, a storage tank 20, a monomer mixer 30, a Venturi tube 40, a polymerization apparatus 50, a gel crusher 60, a drying apparatus 70, and piping connecting these apparatuses. A pipe for discharging the polymer after drying is connected to the drying apparatus 70. The unsaturated monomers supplied to the polymerization apparatus 50 are polymerized to obtain a hydrogel polymer (hereinafter also referred to as "hydrogel"). The hydrogel polymer is crushed by the gel crusher 60. The particulate hydrogel polymer crushed by the gel crusher is transferred to the drying apparatus 70. The drying apparatus 70 is composed of, for example, a paddle dryer, a fluidized bed dryer, a rotary dryer, and a steam tube dryer, and stirs and dries the hydrogel.
[0078] A pipe 11 for supplying a decomposition agent and a pipe 12 for supplying the recovered water absorbent resin, which is the raw material, are connected to the solubilization reaction tank 10. The solubilization reaction tank 10 and the storage tank 20 are also connected by pipes, and the solubilized polymer decomposed in the solubilization reaction tank 10 is transferred to the storage tank 20. The storage tank 20 has a heating means (insulation means) and heats the solubilized polymer to bring it into a heated state.
[0079] The storage tank 20 is a device for storing for a certain period the solubilized polymer that has completed the decomposition reaction in the solubilization reaction tank 10. The storage period in the storage tank is appropriately set in consideration of the production scale, heating conditions, etc., and may be, for example, 30 minutes or more, or may be 60 minutes or more and 1 day or less.
[0080] 1, the solubilized polymer is heated in the storage tank 20, but any form may be used as long as the solubilized polymer is incorporated in a heated state into the production process of the water absorbent resin. For example, the solubilized polymer may be heated in advance before the storage tank 20, and kept warm in the storage tank to maintain the heated state.
[0081] The storage vessel (for example, a tank) may be in a spherical, conical, cylindrical, etc. The heating method, the method or the presence / absence of stirring or circulation of the liquid, the volume, the filling rate, and the like of the storage vessel are appropriately determined.
[0082] The filling rate, storage amount and time per tank are appropriately determined, for example, from 100 L to 20,000 L, or further from 500 L to 15,000 L, depending on the daily production amount of the water absorbent resin.
[0083] The storage tank 20 preferably has a heating means and / or a heat-retaining means. By having the heating means and / or the heat-retaining means, the solubilized polymer can be brought into a heated state and the heated state can be maintained. The heating means and / or the heat-retaining means are not particularly limited, but from the viewpoint of preventing adhesion and aggregation of the solubilized polymer, a heating means using direct heat transfer by convection and / or indirect heat transfer by heat conduction from the heating surface (contact surface with the hydrogel, heat source part) of the storage tank heated by a heat medium is preferred. More preferred heating means are a ventilation heating type for direct heat transfer and an outer wall heating type for indirect heat transfer.
[0084] Preferably, the outer surface of the main body of the storage tank is provided with a heating means and / or a heat retention means, more preferably with a heating means. An example of this heat retention means is a method of covering a part or the entire surface of the outer surface of the main body (preferably 50% or more of the outer surface (area) of the main body, more preferably 80% or more, particularly preferably the entire surface) with a heat insulating material. Examples of the heating means include an electric trace, a steam trace, a jacket heated by a heat medium, and the like, which are installed so as to cover a part or the entire surface of the outer surface of the main body (preferably 50% or more of the outer surface (area) of the main body, more preferably 80% or more, particularly preferably the entire surface).
[0085] Specifically, the heating means and / or heat retention means are provided on the outer surface of the main body (for example, a jacket), and a liquid heat medium such as hot water or oil may be introduced into the jacket or the like installed on the outer surface of the main body, or a heated gas (hot air) may be introduced as a heat medium. These heat media act as heat media for indirect heat transfer. The temperature of the heat medium is preferably 30°C or higher and 200°C or lower, more preferably 50°C or higher and 170°C or lower, even more preferably 50°C or higher and 150°C or lower, and particularly preferably 60°C or higher and 130°C or lower. By being above the above lower limit, the heating efficiency and / or heat retention efficiency of indirect heat transfer is excellent. In addition, by being below the above upper limit, excessive temperature rise and drying of the solubilized polymer are suppressed. Particularly preferred heat media are hot water or steam. In addition, the temperature of the heat medium may be a constant temperature or may be changed appropriately during the process.
[0086] In addition, before the solubilized polymer is introduced into the storage device, the temperature inside (inner surface) of the main body is preferably heated to 30°C or higher, more preferably 50°C or higher, and even more preferably 60°C or higher. This allows the solubilized polymer to be heated efficiently. In addition, when the storage tank has a stirring means, it is preferable that the outer surface of the stirring means is heated to the above-mentioned temperature or higher. In addition, the temperature inside (inner surface) of the main body and / or the outer surface of the stirring means is preferably 30°C or higher and 200°C or lower, more preferably 50°C or higher and 170°C or lower, even more preferably 50°C or higher and 150°C or lower, and particularly preferably 60°C or higher and 130°C or lower.
[0087] When heating in the storage tank, the mixture may be stirred or may be heated without stirring. When stirring is performed using a stirring blade or the like, the stirring portion may also be heated. When stirring is performed as necessary, the rotation speed and time are appropriately determined, for example, at 0.1 rpm or more and 5000 rpm or less, or even at 1 rpm or more and 1000 rpm or less, for 1 second or more and 10 hours or less. Furthermore, heating may be performed continuously or intermittently. Both continuous heating and batch heating are included in the concept of storage in the present invention.
[0088] The solubilized polymer heated in the storage tank 20 is in a heated state. Here, the heated state refers to the temperature of the solubilized polymer being heated to preferably 30°C or more and 100°C or less, more preferably 50°C or more and 100°C or less, even more preferably 55°C or more and 100°C or less, and particularly preferably 55°C or more and 80°C or less. In addition, when the solubilized polymer is "mixed in a heated state", the temperature of the solubilized polymer during mixing is preferably 30°C or more and 100°C or less, more preferably 50°C or more and 100°C or less, even more preferably 55°C or more and 100°C or less, and particularly preferably 55°C or more and 80°C or less. The temperature of the solubilized polymer during mixing is measured, for example, by a thermometer installed at the raw material supply port of the mixing device (for example, a Venturi tube).
[0089] The solubilized polymer heated in the storage tank 20 is transferred to the Venturi tube 40 through the heat-insulating pipeline 21. The heat-insulating pipeline may, for example, have a heat-insulating means in the piping. Examples of the heat-insulating means include those described in the section on the storage tank above. Specifically, examples of the heat-insulating means include a heat-insulating means using direct heat transfer by heat transfer and / or an indirect heat transfer by heat conduction from the heating surface (contact surface, heat source portion) of the piping heated by the heat medium. More preferred heat-insulating means are a ventilation heating type for direct heat transfer and an outer wall heating type for indirect heat transfer.
[0090] Preferably, the outer surface of the pipe is provided with a heat-insulating means. Examples of the heat-insulating means include a method of covering a part or the whole of the outer surface (preferably 50% or more, more preferably 80% or more, particularly preferably the whole) with a heat insulating material, an electric trace or steam trace installed so as to cover a part or the whole of the outer surface of the pipe (preferably 50% or more, more preferably 80% or more, particularly preferably the whole) of the outer surface of the main body, heating with a heat medium, and the like.
[0091] The insulated pipeline has a strainer 22. It is preferable that the solubilized polymer passes through the strainer to filter out water-insoluble materials such as pulp that may be present in the solubilized polymer. The filtration of the heated solubilized polymer is not limited to this form, and may be performed at any time before mixing in the manufacturing process. In this way, by filtering the solubilized polymer before mixing, water-insoluble materials such as pulp that may be present in the solubilized polymer can be filtered out. Therefore, in a preferred embodiment of the present invention, the heated solubilized polymer is mixed in the manufacturing process after filtering.
[0092] The strainer can be a bag filter or a candle filter. The bag filter can be a fully welded, preferably multi-layered, filter bag as well as a sewn filter bag made of various materials. The filter candles can be wound candles, melt-blown candles and resin-bonded filter candles. The filter bags and filter candles can be used in single-layer filter casings as well as multi-layer filter casings. Polypropylene, stainless steel, for example, can be used as the casing material.
[0093] As filter media, for example, stainless steel, polypropylene, cellulose, polyester, metal fabrics (stainless steel, e.g. chromium-nickel-stainless steel) as well as phenolic resin-bonded acrylic fibers etc. come into consideration. A more particularly advantageous material for the filters (filter bags as well as filter candles) to be used according to the invention is polypropylene. In the case of filter candles, activated carbon can also be used.
[0094] Filtration through the strainer is preferably performed with a pressure difference between the fluid before and after the strainer, and the pressure difference is preferably 10 mbar to 5 bar, more preferably 20 mbar to 3 bar, even more preferably 20 mbar to 2 bar, and particularly preferably 20 mbar to 1.5 bar. If a higher pressure difference is required, the filter should be replaced.
[0095] In the embodiment of FIG. 1, the strainer is provided in the heat-insulating pipeline, but the installation position of the filtering means such as the strainer is not particularly limited, and may be any position before the solubilized polymer is mixed in the production process of the water absorbent resin.
[0096] Raw materials (e.g., water, an internal crosslinking agent, etc.) are transferred from a pipe 31 for supplying an unsaturated monomer and other pipes (not shown) and mixed in a monomer mixer 30. To a Venturi tube 40, a solubilized polymer is transferred from a heat-insulating pipeline 21, and an aqueous solution containing an unsaturated monomer is transferred from the monomer mixer 30.
[0097] As shown in FIG. 3, the Venturi tube 40 has a contraction section 41 whose diameter is reduced in the flow direction, a constriction section 42 whose diameter is maintained at the reduced diameter, and an expansion section 43 whose diameter gradually increases from the diameter of the constriction section. The length of the expansion section 43 is longer than the length of the contraction section 41. The heat-insulating pipeline 21 is connected to the constriction section 42, and the heated solubilized polymer is supplied to the Venturi tube 40. The Venturi tube has the above-mentioned structure, so that a pressure difference and / or turbulence occurs at the constriction section, and the two are uniformly mixed at that section. In particular, since the solubilized polymer has viscosity, it is easy to mix uniformly by mixing in the Venturi tube. Therefore, in a preferred embodiment of the present invention, the solubilized polymer and the unsaturated monomer-containing aqueous solution are continuously supplied to the piping and mixed in the piping. The piping is not limited to the Venturi tube, and is not particularly limited as long as the solubilized polymer and the unsaturated monomer-containing aqueous solution are mixed.
[0098] The structure of the Venturi tube is not limited to the form shown in Fig. 3, and various forms may be adopted, such as a form in which the diameter of the constriction portion 42 is not constant. In addition, the supply of the solubilized polymer to the Venturi tube 40 is not limited to one location, and the solubilized polymer may be supplied to the Venturi tube 40 from multiple locations via multiple heat-insulating pipelines.
[0099] The mixing of the solubilized polymer and the unsaturated monomer-containing aqueous solution is not limited to mixing using a Venturi tube, and may be performed using a horizontal or vertical high-speed stirring continuous mixer, etc. Specific examples of the high-speed stirring continuous mixer include a Schuggi mixer and a Turbulizer (both manufactured by Hosokawa Micron Corporation), and a Loedige mixer (manufactured by Loedige).
[0100] Next, the mixture of the unsaturated monomer-containing aqueous solution and the solubilized polymer supplied from the Venturi tube 40, and the polymerization initiator supplied from the pipe 51 are continuously supplied to the polymerization apparatus 50 via the pipes, respectively, and mixed to carry out a polymerization reaction to obtain a hydrogel (polymerization process).
[0101] The resulting hydrogel is then continuously supplied to a gel crusher 60. The crushed hydrogel is then continuously supplied to the next step (drying device 70) via piping (drying step).
[0102] In the above-described embodiment, continuous polymerization (continuous production method) is adopted. The continuous production method is a method in which an unsaturated monomer-containing aqueous solution is continuously transferred into a polymerization apparatus, polymerized, and the hydrogel formed by the polymerization reaction is continuously discharged from the polymerization apparatus. In this case, each step and each operation between steps can be continuously performed, so that troubles such as blockages caused by the stoppage and restart of each apparatus can be avoided.
[0103] When the operation is carried out continuously, the operation time is preferably 1 hour or more, more preferably 3 hours or more, and is usually 1 year or less.
[0104] Next, the embodiment 1-2 will be described with reference to the drawings.
[0105] Fig. 2 is a schematic diagram showing a part of a manufacturing process of a water-absorbent resin according to another embodiment of the present invention. The manufacturing process shown in Fig. 2 includes a solubilization reaction tank 10, a storage tank 20, a monomer mixer 30, a polymerization device 50, a gel crusher 60, a drying device 70, and piping connecting these devices. In the embodiment of Fig. 2, the solubilized polymer heated in the storage tank 20 is transferred to the gel crusher 60 through a heat-insulating pipeline 21. In the gel crusher 60, the hydrogel obtained in the polymerization device 50 and the solubilized polymer are mixed.
[0106] In the embodiment shown in FIG. 2, the hydrogel is mixed with the solubilized polymer in a gel crushing device. However, the hydrogel may be mixed with the solubilized polymer in a shredding device in the shredding step described below.
[0107] Each step will now be described in detail.
[0108] [3-1] Preparation of monomer aqueous solution This step is an optional step for preparing an aqueous solution containing an unsaturated monomer as a raw material for the water absorbent resin, preferably an aqueous solution containing an acid group-containing unsaturated monomer as a main component. Although a monomer slurry liquid can be used within a range in which the water absorption performance of the obtained water absorbent resin is not deteriorated, for the sake of convenience, the aqueous monomer solution will be described in this section.
[0109] The above-mentioned "main component" means that the amount (content) of the acid group-containing unsaturated monomer used is usually 50 mol % or more, preferably 70 mol % or more, and more preferably 90 mol % or more (upper limit: 100 mol %) based on the total monomers (excluding the internal crosslinking agent) to be subjected to the polymerization reaction of the water absorbent resin.
[0110] (Acid group-containing unsaturated monomer) The acid group defined in the present invention is not particularly limited, but examples thereof include a carboxyl group, a sulfone group, and a phosphoric acid group. Examples of the acid group-containing unsaturated monomer include (meth)acrylic acid, (anhydrous) maleic acid, itaconic acid, cinnamic acid, vinyl sulfonic acid, allyl toluene sulfonic acid, vinyl toluene sulfonic acid, styrene sulfonic acid, 2-(meth)acrylamido-2-methylpropanesulfonic acid, 2-(meth)acryloylethanesulfonic acid, 2-(meth)acryloylpropanesulfonic acid, and 2-hydroxyethyl (meth)acryloyl phosphate. From the viewpoint of water absorption performance, preferred are (meth)acrylic acid, (anhydrous) maleic acid, itaconic acid, and cinnamic acid, more preferred are (meth)acrylic acid, and particularly preferred is acrylic acid.
[0111] (Monomers other than acid group-containing unsaturated monomers) The monomer other than the acid group-containing unsaturated monomer may be any compound that can be polymerized to become a water-absorbing resin. For example, amide group-containing unsaturated monomers such as (meth)acrylamide, N-ethyl (meth)acrylamide, and N,N-dimethyl (meth)acrylamide; amino group-containing unsaturated monomers such as N,N-dimethylaminoethyl (meth)acrylate, N,N-dimethylaminopropyl (meth)acrylate, and N,N-dimethylaminopropyl (meth)acrylamide; mercapto group-containing unsaturated monomers; phenolic hydroxyl group-containing unsaturated monomers; lactam group-containing unsaturated monomers such as N-vinylpyrrolidone; etc.
[0112] (Basic Composition) In one embodiment of the present invention, the term "basic composition" refers to a composition containing a basic compound, such as a commercially available aqueous sodium hydroxide solution. Specific examples of the basic compound include alkali metal salts such as alkali metal carbonates and / or hydrogen carbonates, and alkali metal hydroxides such as sodium hydroxide, potassium hydroxide, and lithium hydroxide. Other examples of basic compounds include ammonia and organic amines.
[0113] (neutralization) As the neutralization in one embodiment of the present invention, either neutralization (before polymerization) of an unsaturated monomer (e.g., acrylic acid) or neutralization (after polymerization) of a hydrogel-like crosslinked polymer obtained by crosslinking and polymerizing an unsaturated monomer (hereinafter referred to as "post-neutralization") can be selected or used in combination. When a solubilized polymer is used as at least a part of a raw material for the production of a water-absorbent resin, if the solubilized polymer contains a basic compound, this basic compound neutralizes the unsaturated monomer before polymerization or the hydrogel-like crosslinked polymer after polymerization. Therefore, the neutralization rate of the water-absorbent resin as a final product may be adjusted to a predetermined range by adding this basic compound. Regarding the conditions such as the apparatus for performing neutralization, the neutralization temperature, and the residence time, the conditions described in International Publication No. 2009 / 123197, US Patent Application Publication No. 2008 / 0194863, etc. may also be applied to the present invention. The neutralization in one embodiment of the present invention may be performed by adding a basic compound to the aqueous monomer solution in multiple stages.
[0114] In one embodiment of the present invention, the neutralization rate is preferably 10 mol% to 90 mol%, more preferably 40 mol% to 85 mol%, even more preferably 50 mol% to 80 mol%, and particularly preferably 60 mol% to 75 mol% based on the acid group of the monomer. Note that a neutralization rate of 75 mol% means 25 mol% of acrylic acid and 75 mol% of acrylic acid salt. This may also be referred to as a partially neutralized product of acrylic acid. The above neutralization rate is the same in the case of post-neutralization.
[0115] (Internal crosslinking agent) In the method for producing the water-absorbent resin, an internal crosslinking agent is preferably used, which adjusts the water-absorbency performance and gel strength of the obtained water-absorbent resin when it absorbs water.
[0116] The internal crosslinking agent may have a total of two or more unsaturated bonds or reactive functional groups in one molecule. For example, examples of internal crosslinking agents having a plurality of polymerizable unsaturated groups (copolymerizable with monomers) in the molecule include N,N-methylenebis(meth)acrylamide, (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, glycerin (meth)acrylate, glycerin acrylate methacrylate, ethylene oxide modified trimethylolpropane tri(meth)acrylate, pentaerythritol hexa(meth)acrylate, triallyl cyanurate, triallyl isocyanurate, and triallyl phosphate. Examples of internal crosslinking agents having multiple reactive functional groups (which can react with functional groups of monomers (e.g., carboxy groups)) in the molecule include triallylamine, polyallyloxyalkane, (poly)ethylene glycol diglycidyl ether, glycerol diglycidyl ether, ethylene glycol, polyethylene glycol, propylene glycol, glycerin, 1,4-butanediol, pentaerythritol, ethylenediamine, ethylene carbonate, propylene carbonate, and polyethyleneimine (note that here, cyclic carbonates such as ethylene carbonate are crosslinking agents that further generate functional groups OH by reacting with carboxyl groups). Examples of internal crosslinking agents having polymerizable unsaturated groups and reactive functional groups in the molecule include glycidyl (meth)acrylate. Two or more of these may be used in combination.
[0117] Among these internal crosslinking agents, from the viewpoint of the effects of the present invention, a compound having a plurality of polymerizable unsaturated groups in the molecule is preferable, a compound having a (poly)alkylene structural unit in the molecule is more preferable, and a compound having a polyethylene glycol structural unit is even more preferable.
[0118] The amount of the internal crosslinking agent used is appropriately set depending on the type of monomer and the internal crosslinking agent. From the viewpoint of gel strength of the obtained water absorbent resin, the amount is preferably 0.001 mol% or more, more preferably 0.005 mol% or more, and even more preferably 0.01 mol% or more, based on the monomer (excluding the internal crosslinking agent). From the viewpoint of improving the water absorption performance of the water absorbent resin, the amount is preferably 5 mol% or less, more preferably 2 mol% or less. Note that, under polymerization conditions where the self-crosslinking reaction of the monomer is effective, the internal crosslinking agent may not be used.
[0119] (Polymerization inhibitor) The monomer used in the polymerization may contain a small amount of a polymerization inhibitor for the stability of the polymerization. A preferred polymerization inhibitor is p-methoxyphenol. The amount of the polymerization inhibitor contained in the monomer (particularly acrylic acid and its salts) is usually 1 ppm or more and 250 ppm or less, preferably 10 ppm or more and 160 ppm or less (by mass), more preferably 20 ppm or more and 80 ppm or less.
[0120] (Other substances added to the monomer aqueous solution) In one embodiment of the present invention, the following substances may be added during the preparation of the aqueous monomer solution.
[0121] Specifically, any of hydrophilic polymers such as starch, starch derivatives, cellulose, cellulose derivatives, polyvinyl alcohol, polyacrylic acid (salts), and crosslinked polyacrylic acid (salts) can be added in an amount of preferably 50% by mass or less, more preferably 20% by mass or less, even more preferably 10% by mass or less, and particularly preferably 5% by mass or less (lower limit: 0% by mass); any of carbonates, azo compounds, foaming agents such as air bubbles, surfactants, chelating agents, and chain transfer agents can be added in an amount of preferably 5% by mass or less, more preferably 1% by mass or less, and even more preferably 0.5% by mass or less (lower limit: 0% by mass, more than 0% by mass, 0.005% by mass or more, or 0.01% by mass or more).
[0122] In addition, the following substances (hereinafter referred to as "other substances") may be added to the aqueous monomer solution. Specific examples of other substances include chain transfer agents such as thiols, thiolic acids, secondary alcohols, amines, and hypophosphites; foaming agents such as carbonates, bicarbonates, azo compounds, and bubbles; chelating agents such as amino polycarboxylic acids (salts) such as metal salts of ethylenediaminetetraacetic acid and metal salts of diethylenetriaminepentaacetic acid, and amino polyphosphonic acids (salts) such as ethylenediaminetetra(methylenephosphonic acid); thickeners such as polyacrylic acid (salts) and crosslinked products thereof, starch, cellulose, starch-cellulose derivatives, and polyvinyl alcohol. The other substances may be used alone or in combination of two or more.
[0123] The amount of other substances used is not particularly limited, but the total concentration of the other substances is preferably from 0.0001% by mass to 10% by mass, more preferably from 0.0005% by mass to 1% by mass, and even more preferably from 0.001% by mass to 0.1% by mass, relative to the monomer (excluding the internal crosslinking agent).
[0124] The above-mentioned substances and chelating agents may be added not only to the aqueous monomer solution but also during the polymerization, or these forms may be used in combination.
[0125] Dissolved oxygen in the aqueous monomer solution (optionally containing the solubilized polymer) may be reduced by raising the temperature or replacing it with an inert gas.
[0126] The concentration of the monomer in the aqueous monomer solution (excluding the solubilized polymer) is selected depending on the selected monomer, decomposition product, and organic solvent type, etc. In terms of production efficiency, the lower limit is preferably 10% by mass or more, more preferably 20% by mass or more, and even more preferably 30% by mass or more. The upper limit is preferably 100% by mass or less, more preferably 90% by mass or less, even more preferably 80% by mass or less, and even more preferably 70% by mass or less.
[0127] As long as the object of the present invention is not hindered, additives such as surfactants, density regulators, thickeners, etc. can be added to the aqueous monomer solution. The type and amount of the additives can be appropriately selected depending on the combination of the monomers and organic solvents used.
[0128] [3-2] Polymerization process This step is a step of polymerizing the unsaturated monomer-containing aqueous solution obtained in the above-mentioned monomer aqueous solution preparation step to obtain a hydrogel-like crosslinked polymer (hydrogel). In the polymerization step, a monomer composition containing an unsaturated monomer-containing aqueous solution and a polymerization initiator is polymerized.
[0129] In the form 1-2, the heated solubilized polymer is added in the polymerization step (particularly, the monomer composition in the polymerization device). Here, the timing of adding the heated solubilized polymer is not particularly limited, but specifically, the heated solubilized polymer is added just before the polymerization of the monomer composition (specifically, for example, the form of adding it simultaneously with the polymerization initiator); the heated solubilized polymer is added during the polymerization of the monomer (specifically, for example, the form of adding the heated solubilized polymer in the gel crushing step during the polymerization step, such as the case of performing polymerization and gel crushing simultaneously, such as continuous kneader polymerization), and combinations thereof.
[0130] (Polymerization initiator) The polymerization initiator used in one embodiment of the present invention is not particularly limited since it is appropriately selected depending on the polymerization form, etc. For example, a thermally decomposable polymerization initiator, a photodecomposable polymerization initiator, or a redox-based polymerization initiator using a reducing agent (e.g., L-ascorbic acid, sodium hydrogen sulfite, etc.) that promotes the decomposition of these polymerization initiators in combination, etc., can be mentioned. Specifically, one or more of the polymerization initiators disclosed in U.S. Pat. No. 7,265,190 are used. From the viewpoint of the handleability of the polymerization initiator, the physical properties of the water-absorbing resin, etc., preferably a peroxide or an azo compound is used, more preferably a peroxide, and even more preferably a persulfate.
[0131] The amount of the polymerization initiator used is preferably 0.001 mol% or more and 1 mol% or less, more preferably 0.001 mol% or more and 0.5 mol% or less, based on the monomer. The amount of the reducing agent used is preferably 0.0001 mol% or more and 0.02 mol% or less, based on the monomer. Note that instead of the polymerization initiator, the polymerization reaction may be carried out by irradiating active energy rays such as radiation, electron beams, and ultraviolet rays, and these active energy rays and the polymerization initiator may be used in combination.
[0132] (polymerization form) The polymerization form applied to one embodiment of the present invention is not particularly limited, but from the viewpoint of water absorption characteristics, ease of polymerization control, etc., preferably, spray droplet polymerization, aqueous solution polymerization, and reversed phase suspension polymerization, more preferably, aqueous solution polymerization, and reversed phase suspension polymerization, and further preferably, aqueous solution polymerization are mentioned. Among them, continuous aqueous solution polymerization is particularly preferable, and either continuous belt polymerization or continuous kneader polymerization is applicable.
[0133] As specific polymerization forms, continuous belt polymerization is disclosed in U.S. Patent Nos. 4,893,999, 6,241,928, U.S. Patent Application Publication No. 2005 / 215734, etc., and continuous kneader polymerization is disclosed in U.S. Patent Nos. 6,987,151, 6,710,141, etc. By adopting these continuous aqueous solution polymerizations, the production efficiency of the water absorbent resin is improved.
[0134] In addition, preferred forms of the continuous aqueous solution polymerization include "high-temperature initiated polymerization" and "high-concentration polymerization". "High-temperature initiated polymerization" refers to a form in which polymerization is initiated at a temperature of the aqueous monomer solution of preferably 30°C or higher, more preferably 35°C or higher, even more preferably 40°C or higher, and particularly preferably 50°C or higher (upper limit is the boiling point). "High-concentration polymerization" refers to a form in which polymerization is performed at a monomer concentration of preferably 30% by mass or higher, more preferably 35% by mass or higher, even more preferably 40% by mass or higher, and particularly preferably 45% by mass or higher (upper limit is the saturated concentration). These polymerization forms can also be used in combination. For example, the polymerization temperature is preferably 20°C or higher and 100°C or lower, more preferably 40°C or higher and 90°C or lower.
[0135] In one embodiment of the present invention, the polymerization can be carried out under an air atmosphere, but from the viewpoint of the color tone of the obtained water absorbent resin, it is preferable to carry out the polymerization under an inert gas atmosphere such as nitrogen or argon. In this case, for example, it is preferable to control the oxygen concentration to 1 volume % or less. It is also preferable to replace the dissolved oxygen in the aqueous monomer solution with an inert gas (for example, dissolved oxygen; less than 1 mg / l).
[0136] In one embodiment of the present invention, the polymerization may be carried out as foaming polymerization in which bubbles (particularly the above-mentioned inert gases or the like) are dispersed in an aqueous monomer solution.
[0137] [3-3] Hydrogel crushing process In this step, the hydrogel obtained in the polymerization step is gel-pulverized by a gel-pulverizing device such as a screw extruder such as a kneader or meat chopper, or a cutter mill, to obtain a particulate hydrogel (hereinafter referred to as "particulate hydrogel"). When the polymerization step is kneader polymerization, the polymerization step and the gel-pulverizing step are performed simultaneously. In addition, when a particulate hydrogel is obtained directly in the polymerization process, such as gas-phase polymerization or reversed-phase suspension polymerization, the gel-pulverizing step may not be performed. If necessary, a shredding step may be performed using a roller cutter, a guillotine cutter, or the like to cut or roughly crush the hydrogel-like crosslinked polymer into a size that can be put into a gel-pulverizing device after the polymerization step and before the gel-crushing step. In particular, when the polymerization step is belt polymerization and a sheet-like or block-like hydrogel is obtained, it is preferable to perform the shredding step.
[0138] Regarding gel crushing conditions and forms other than those described above, the contents disclosed in WO 2011 / 126079 are preferably applied to the present invention.
[0139] In form 2, the solubilized polymer is added to the hydrogel. The addition of the heated solubilized polymer in the gel crushing step is not limited to the form of adding the hydrogel and the heated solubilized polymer to the gel crushing device, and the form of adding the heated solubilized polymer before the hydrogel after the polymerization step to be gel-crushed is fed into the gel crushing device and mixing the heated solubilized polymer into the hydrogel at the same time as gel crushing is also included in the addition of the heated solubilized polymer in the gel crushing step referred to in the present invention. The heated solubilized polymer may be added in a shredding step in which the hydrogel is cut or roughly crushed to a size that can be fed into the gel crushing device before the gel crushing step. When the addition is performed in the gel crushing step, it is preferable to add the heated solubilized polymer before and / or during the gel crushing step and mix it thoroughly during gel crushing.
[0140] The amount of the solubilizing polymer added (solid content) is preferably from 1 to 60% by mass, more preferably from 3 to 50% by mass, and even more preferably from 5 to 40% by mass, based on the solid content of the hydrogel.
[0141] [3-4] Drying process This step is a step of obtaining a dry polymer by drying the particulate hydrogel obtained in the polymerization step and / or hydrogel crushing step to a desired resin solid content. The resin solid content is determined from the loss on drying (the change in mass when 1 g of the water-absorbent resin is heated at 180°C for 3 hours), and is preferably 80% by mass or more, more preferably 85% by mass to 99% by mass, even more preferably 90% by mass to 98% by mass, and particularly preferably 92% by mass to 97% by mass.
[0142] The method for drying the particulate hydrogel is not particularly limited, and examples thereof include heat drying, hot air drying, reduced pressure drying, fluidized bed drying, infrared drying, microwave drying, drum dryer drying, drying by azeotropic dehydration with a hydrophobic organic solvent, high humidity drying using high temperature water vapor, etc. Among these, from the viewpoint of drying efficiency, hot air drying is preferred, and band drying in which hot air drying is performed on a ventilation belt is more preferred.
[0143] The drying temperature (hot air temperature) in the hot air drying is preferably 120° C. or higher and 250° C. or lower, more preferably 150° C. or higher and 200° C. or lower, from the viewpoints of the color tone of the water-absorbent resin, drying efficiency, etc. In addition, drying conditions other than the drying temperature, such as the hot air speed and drying time, may be appropriately set depending on the water content and total mass of the particulate hydrogel to be dried and the target resin solid content, and when band drying is performed, the various conditions described in WO 2006 / 100300, WO 2011 / 025012, WO 2011 / 025013, WO 2011 / 111657, etc. are appropriately applied.
[0144] By setting the above-mentioned drying temperature, drying time, etc., within the above-mentioned ranges, it is possible to set the AAP0.3 (absorbency under pressure), CRC (absorbency without pressure) and yellowness index (YI value) of the obtained water absorbent resin within desired ranges (see the following [4-1], [4-2] and [4-3]).
[0145] [3-5] Surface crosslinking process This step is a step of providing a portion with a higher crosslink density on a surface layer (a portion several tens of μm from the surface of the water absorbent resin) of the water absorbent resin (sometimes referred to as a water absorbent resin precursor) obtained through the above-mentioned steps, and is composed of a mixing step, a heat treatment step, and a cooling step (optional).
[0146] In the surface cross-linking step, a surface-cross-linked water-absorbent resin is obtained by radical cross-linking, surface polymerization, cross-linking reaction with a surface cross-linking agent, or the like on the surface of the water-absorbent resin.
[0147] (Surface cross-linking agent) The surface cross-linking agent used in one embodiment of the present invention is not particularly limited, but may be an organic or inorganic surface cross-linking agent. Among them, from the viewpoint of the physical properties of the water-absorbent resin, the handling property of the surface cross-linking agent, etc., an organic surface cross-linking agent that reacts with a carboxyl group is preferred. For example, one or more surface cross-linking agents disclosed in U.S. Patent No. 7,183,456 may be mentioned. More specifically, polyhydric alcohol compounds, epoxy compounds, haloepoxy compounds, polyamine compounds or their condensates with haloepoxy compounds, oxazoline compounds, oxazolidinone compounds, polyvalent metal salts, alkylene carbonate compounds, cyclic urea compounds, etc. may be mentioned.
[0148] The amount of the surface crosslinking agent used (when a plurality of agents are used, the total amount used) is preferably 0.01 to 10 parts by mass, more preferably 0.01 to 5 parts by mass, relative to 100 parts by mass of the water absorbent resin. The surface crosslinking agent is preferably added as an aqueous solution, and in this case, the amount of water used is preferably 0.1 to 20 parts by mass, more preferably 0.5 to 10 parts by mass, relative to 100 parts by mass of the water absorbent resin. Furthermore, when a hydrophilic organic solvent is used as necessary, the amount used is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, relative to 100 parts by mass of the water absorbent resin.
[0149] In addition, each of the additives described below can be added by mixing it with the surface cross-linking agent (aqueous solution) in an amount of 5 parts by mass or less, or can be added separately in this mixing step.
[0150] (Mixing process) This step is a step of mixing the water absorbent resin and the above-mentioned surface crosslinking agent. The method of mixing the surface crosslinking agent is not particularly limited, but includes a method of preparing a surface crosslinking agent solution in advance, and mixing the liquid with the water absorbent resin by preferably spraying or dropping, more preferably spraying.
[0151] The device for carrying out the mixing is not particularly limited, but is preferably a high-speed stirring type mixer, more preferably a high-speed stirring type continuous mixer.
[0152] (Heat treatment process) In this step, heat is applied to the mixture discharged from the mixing step to cause a crosslinking reaction in the vicinity of the surface of the water-absorbent resin.
[0153] The device for carrying out the crosslinking reaction is not particularly limited, but preferably includes a paddle dryer. The reaction temperature in the crosslinking reaction is appropriately set depending on the type of the surface crosslinking agent used, but is preferably 50°C or higher and 300°C or lower, more preferably 100°C or higher and 200°C or lower.
[0154] (cooling process) This step is an optional step that is installed as necessary after the heat treatment step. The cooling device is not particularly limited, but is preferably a device with the same specifications as the device used in the heat treatment step, and more preferably a paddle dryer. This is because it can be used as a cooling device by changing the heat medium to a refrigerant. The water-absorbent resin obtained in the heat treatment step is forcibly cooled, as necessary, to preferably 40°C or more and 80°C or less, more preferably 50°C or more and 70°C or less, in the cooling step.
[0155] After the surface cross-linking step, a sizing step may be further carried out. In addition to the above, the method according to the present invention may include at least one step selected from the steps of adding various additives, removing fine powder, recycling fine powder (recovering fine powder), and filling. Furthermore, various known steps may be included depending on the purpose. The fine powder removed in the removing fine powder step may be used as a recovered water absorbent resin.
[0156] [3-6] Sizing process This step is a step for adjusting the particle size of the surface-crosslinked water-absorbent resin. This particle size regulation step provides a water-absorbent resin whose particle size or particle size distribution is more actively controlled.
[0157] Preferably, the sizing step includes a crushing step and / or a classification step. The crushing step is a step of adjusting the particle size by crushing the loosely aggregated granular material after the surface cross-linking step with a crusher. The classification step is a step of removing coarse particles and fine powder from the surface cross-linked granular material or the crushed material thereof with a classifier.
[0158] The crusher is not particularly limited, and examples thereof include a vibration mill, a roll granulator, a knuckle type crusher, a roll mill, a high-speed rotary crusher (pin mill, hammer mill, screw mill), a cylindrical mixer, etc. Those that cause little damage to the dried material or the surface-crosslinked dried material are preferred, and specific examples thereof include a roll granulator (Matsubo Corporation), a granulator (Kurimoto Iron Works, Ltd.), and a Randel Mill (Tokuju Corporation). As a classifier, a vibrating or rocking sieve classifier using a sieve net is used.
[0159] [3-7] Fine powder recycling process The "fine powder recycling process" means a process in which the fine powder removed in the classification step is supplied to any process as it is or after granulating the fine powder. Preferably, it is a process in which the fine powder or the fine powder granules are fed to a process before the drying process to reuse them. Examples of processes before the drying process include a monomer aqueous solution preparation process, a polymerization process, a pulverization process of the hydrogel after polymerization, and a drying process of the granular hydrogel. The fine powder may be added to these processes as it is, or may be added after swelling and gelling with water or granulating. In addition, water, a crosslinking agent, a binder other than water (e.g., a water-soluble polymer, a thermoplastic resin), a polymerization initiator, a reducing agent, a chelating agent, a coloring inhibitor, etc. may be added together with the fine powder. The preferred amount of fine powder recovery is appropriately set depending on the target particle size.
[0160] [3-8] Other processes In addition to the steps described above, the production method according to the present invention may further include a pulverizing step, a classification step, a rewetting step, a granulating step, a transporting step, a storing step, a packaging step, a storage step, and the like, as necessary.
[0161] (Other additives) Other than the above-mentioned optionally used surface crosslinking agent, conventionally known components such as a gel fluidizing agent, a polymer powder (e.g., starch such as tapioca starch acetate), inorganic fine particles, a dust inhibitor, a dried water absorbent resin (fine powder), a liquid permeability improver, a reducing agent (e.g., sodium sulfite), and a chelating agent can be further added as other additives before or after drying.
[0162] [4] Physical properties of water-absorbent resin It is desirable that the water-absorbent resin obtained by the production method according to the present invention satisfies at least one of the following [4-1] and [4-2] when the water-absorbent resin is used in absorbent articles, particularly disposable diapers.
[0163] [4-1] AAP0.3 (absorption capacity under pressure) The water-absorbent resin produced by the method according to the present invention can improve AAP0.3 (absorption capacity under pressure). The water-absorbent resin produced by the method according to the present invention may have AAP0.3 (absorption capacity under pressure) of 10 g / g or more, 15 g / g or more, 20 g / g or more, 22 g / g or more, 24 g / g or more, 25 g / g or more, 26 g / g or more, or 27 g / g or more. By setting AAP0.3 (absorption capacity under pressure) to such a lower limit, the amount of liquid returning when pressure is applied to the absorbent body (sometimes referred to as "Re-Wet") can be kept low, and the water-absorbent resin becomes suitable for absorbent body applications in absorbent articles such as disposable diapers and sanitary napkins. In one embodiment, the water-absorbent resin has AAP0.3 (absorption capacity under pressure) of 40 g / g or less, 35 g / g or less, or 30 g / g or less. The AAP0.3 (absorbency against pressure) can be controlled by known techniques, for example, by the crosslinking density of the surface crosslinked layer.
[0164] [4-2] CRC (absorption capacity without pressure) The absorbency without load (CRC) of the water-absorbent resin produced by the method according to the present invention is usually 5 g / g or more, and may be 15 g / g or more, 25 g / g or more, 28 g / g or more, or 30 g / g or more. The upper limit is not particularly limited, and a higher CRC is preferable, but from the viewpoint of balance with other physical properties, it is preferably 70 g / g or less, more preferably 50 g / g or less, and even more preferably 40 g / g or less. If the CRC is less than 5 g / g, the absorption amount is small and it is not suitable for use as an absorbent for absorbent articles such as disposable diapers. In addition, if the CRC exceeds 70 g / g, the speed of absorbing body fluids such as urine and blood decreases, so it is not suitable for use in disposable diapers with high water absorption speed.
[0165] [4-3] Yellowness index (YI value) The yellowness index (YI value) in the Hunter Lab color system of the water absorbent resin produced by the method according to the present invention is preferably 15 or less, more preferably 14 or less, and further preferably 12 or less. The aqueous solution is substantially white with a low coloring as the yellowness index approaches 0.
[0166] Although the embodiments of the present invention have been described in detail, it is apparent that the same are illustrative and exemplary, not restrictive, and the scope of the present invention should be interpreted by the appended claims.
[0167] The present invention encompasses the following aspects and configurations.
[0168] 1. A method for producing a water-absorbent resin, comprising a polymerization step of polymerizing an unsaturated monomer-containing aqueous solution to obtain a hydrogel-like crosslinked polymer, and a drying step of drying the hydrogel-like crosslinked polymer, in which a solubilized polymer of a recovered water-absorbent resin is used as a part of a raw material, A method for producing a water-absorbing resin, wherein the solubilizing polymer is mixed in a heated state at any one of the production steps.
[0169] 2. The manufacturing method according to the above 1, wherein the recovered water-absorbent resin is a used water-absorbent resin recovered from a used absorbent article.
[0170] 3. The method according to 1. or 2. above, wherein the heated solubilized polymer is heated to a temperature of 30°C or higher and 100°C or lower.
[0171] 4. The method according to any one of 1. to 3. above, wherein the temperature of the solubilized polymer in a heated state is controlled within a range of ±10°C.
[0172] 5. The method according to any one of 1. to 4. above, wherein the concentration of the solubilized polymer in a heated state is an aqueous solution of 5% by mass or more.
[0173] 6. The method according to any one of 1. to 5. above, wherein the heated solubilized polymer is mixed in a production step prior to the drying step.
[0174] 7. The production method according to claim 6, wherein the heated solubilized polymer is mixed with the unsaturated monomer and / or the hydrogel-like crosslinked polymer.
[0175] 8. The method according to claim 7, wherein the heated solubilized polymer is mixed with the unsaturated monomer.
[0176] 9. The method according to claim 8, wherein the polymerization initiator is added after the mixing and then the polymerization starts within 5 minutes.
[0177] 10. The method according to any one of 1 to 9 above, wherein the temperature difference between the solubilized polymer and the water-absorbent resin raw material to be mixed with the solubilized polymer is 50° C. or less.
[0178] 11. The method according to any one of 1. to 10. above, wherein the water-absorbent resin raw material to be mixed with the solubilized polymer is in a heated state.
[0179] 12. The manufacturing method described in any one of 1. to 11. above, wherein the solubilized polymer and the unsaturated monomer-containing aqueous solution are continuously supplied to a pipe, and the solubilized polymer and the unsaturated monomer-containing aqueous solution are mixed in the pipe.
[0180] 13. The method according to any one of 1. to 12. above, wherein the solubilized polymer after the decomposition treatment of the recovered water-absorbent resin is stored in a heated state.
[0181] 14. The method according to any one of 1. to 13. above, wherein the decomposition treatment of the recovered water absorbent resin is carried out with an oxidizing agent.
[0182] 15. The method according to any one of 1. to 14. above, wherein the solubilized polymer contains a polymerization inhibitor.
[0183] 16. The method according to any one of 1. to 15. above, wherein the YI value of the solubilized polymer is 10 or less in an aqueous solution state of 8% by mass or more and 10% by mass or less.
[0184] 17. The method according to any one of 1. to 16. above, wherein the transition metal ion content in the solubilized polymer is 10 ppm or less (based on the solid content).
[0185] 18. The method according to any one of 1. to 17. above, wherein the L-ascorbic acid content in the solubilizing polymer is 10 ppm or less (based on solid content).
[0186] 19. The method according to any one of 1. to 18. above, wherein the oxidizing agent in the solubilized polymer is 100 ppm or less (based on solid content).
[0187] 20. The method according to any one of 1. to 19. above, wherein the heated solubilized polymer is mixed in the production process after filtration. EXAMPLES
[0188] The present invention will be described in more detail with reference to the following examples and comparative examples, but the present invention is not limited to these examples, and examples obtained by appropriately combining the technical means disclosed in each example are also included in the scope of the present invention. Furthermore, unless otherwise specified, operations and measurements of physical properties are performed under room temperature (20°C or higher and 25°C or lower) and relative humidity of 45±5% RH. In this specification, the unit of volume "liter" may be written as "l" or "L".
[0189] (a) CRC "CRC" of the water absorbent resin of the present invention is an abbreviation for Centrifuge Retention Capacity, and indicates the absorption capacity (unit: g / g) of the water absorbent resin for a 0.90 mass % aqueous sodium chloride solution under no pressure for 30 minutes.
[0190] 0.200 g of water-absorbent resin was evenly placed in a bag (85 mm x 60 mm) made of nonwoven fabric (manufactured by Nangoku Pulp Industrial Co., Ltd., product name: Heatlon Paper, model: GSP-22), heat-sealed, and then immersed in a large excess (usually about 500 ml) of 0.90% by mass sodium chloride aqueous solution at room temperature. After 30 minutes, the bag was pulled out and drained for 3 minutes at a centrifugal force (250 G) described in ERT441.2-02 using a centrifuge (manufactured by Kokusan Co., Ltd., centrifuge: model H-122), and the mass W1 (g) of the bag was measured. In addition, the same operation was performed without using the water-absorbent resin, and the mass W0 (g) at that time was measured. Then, from these W1 and W0, the CRC (centrifuge retention capacity) was calculated according to the following formula (1). Note that "EDANA" is an abbreviation for European Disposables and Nonwovens Associations.
[0191] CRC(g / g)=(W1-W0) / (mass of water-absorbent resin)-1···Equation (1) (b) AAP0.3 "AAP" of the water absorbent resin of the present invention is an abbreviation for Absorption Against Pressure, and indicates the absorbency against pressure (unit: g / g) for a 0.90 mass % aqueous sodium chloride solution.
[0192] AAP0.3 was measured in accordance with ERT442.2-02. Specifically, a large excess of 0.9% by mass of sodium chloride aqueous solution was used, and 0.9 g of the water-absorbent resin was subjected to 2.07 kPa (21 g / cm 2 After swelling under a pressure of 0.2 psi (0.3 psi), the AAP (absorbency against pressure) was measured.
[0193] (c) Coloring evaluation of water absorbent resin / solubilized polymer (yellowness index / YI value) The color evaluation of the water-absorbent resin / solubilized polymer was carried out using a spectrophotometer SE7700 manufactured by Nippon Denshoku Industries Co., Ltd. The measurement settings included transmission measurement, an attached square cell (light path 10 mm) was used, and industrial pure water was used as the standard. The square cell was filled with approximately 16 g of the water-absorbent resin / solubilized polymer aqueous solution and placed in the sample holder in the transmission sample chamber. The YI value (Yellow Index) was measured using the above spectrophotometer under conditions of room temperature (20°C to 25°C) and humidity of 50 RH%.
[0194] (d) Measurement of the amount of transition metal ions in the solubilized polymer After adding nitric acid to the aqueous solution of the solubilized polymer, the resulting solution was repeatedly heated and irradiated with microwaves in stages to obtain the decomposition products of the solubilized polymer. The amount of transition metal ions in the solubilized polymer was quantified by ICP emission spectroscopy.
[0195] (e) Measurement of the amount of L-ascorbic acid in the solubilized polymer The solubilized polymer was analyzed by liquid chromatography equipped with a UV detector to measure the amount of L-ascorbic acid remaining in the solubilized polymer (ppm by mass vs. solid content).
[0196] (f) Measurement of the amount of oxidizing agent (hydrogen peroxide) in the solubilized polymer 0.50 g of the solubilized polymer aqueous solution, 8.5 g of industrially pure water, and 1.0 g of a 10% by mass aqueous calcium chloride solution were placed in a container and mixed to precipitate the solubilized polymer, which was then filtered through a 0.2 μm chromatodisc.
[0197] 0.30 g of 1 mol / L (2N) sulfuric acid was added to the obtained filtrate, and after mixing, coloring was performed with 0.10 g of 30 mass % titanium (IV) sulfate.
[0198] The absorbance was measured using a ratio beam spectrophotometer U-5100 (Hitachi High-Tech Corporation). The attached 10 mm square cell was used, and industrial pure water was used as the standard. The wavelength was 410 nm.
[0199] Separately, a calibration curve of "amount of hydrogen peroxide vs. absorbance" was prepared using a hydrogen peroxide aqueous solution of known concentration and colored with titanium(IV) sulfate in the same manner as above. The amount of hydrogen peroxide remaining in the solubilized polymer aqueous solution was calculated from the calibration curve.
[0200] (g) Measurement of mass median particle size (D50) and logarithmic standard deviation of particle size distribution (σζ) The mass median particle size (D50) and the logarithmic standard deviation (σζ) of the particle size distribution were measured by a method similar to that described in US Pat. No. 7,638,570.
[0201] (h) Measurement of water soluble matter (16-hour value) 184.3 g of 0.90% by mass sodium chloride solution was weighed out into a 250 ml plastic container with a lid, 1.00 g of water-absorbent resin was added to the aqueous solution, and the mixture was stirred for 16 hours to extract the water-soluble components in the resin. This extract was filtered using a sheet of filter paper (ADVANTEC Toyo Co., Ltd., product name: (JIS P 3801, No. 2), thickness 0.26 mm, retention particle size 5 μm), and 50.0 g of the filtrate was used as the measurement liquid.
[0202] Next, the above measurement solution was titrated with 0.1N-NaOH aqueous solution until the pH reached 10, and then titrated with 0.1N-HCl aqueous solution until the pH reached 2.7. The titration amounts at this time were calculated as [NaOH] ml and [HCl] ml, respectively.
[0203] Furthermore, the same procedure was carried out using only 184.3 g of a 0.90% by mass aqueous sodium chloride solution without adding any water-absorbent resin, and the blank titration amount ([bNaOH] ml, [bHCl] ml) was determined.
[0204] When the water absorbent resin is composed of a known amount of acrylic acid and a salt thereof, the water-soluble content (unit: mass%) in the water absorbent resin can be calculated by the following formula (2) based on the average molecular weight of the monomer and the titration amount obtained by the above operation.
[0205] Formula (2): Water soluble content (mass%) = 0.1 × (average molecular weight of monomers) × 184.3 × 100 × ([HCl]-[bHCl]) / 1000 / 1.0 / 50.0.
[0206] [Production Example 1] A reaction solution was prepared by dissolving 0.44 parts by mass of polyethylene glycol diacrylate (molecular weight 523) in 550 parts by mass of a 38% by mass aqueous solution of sodium acrylate (neutralization rate 71 mol%). Next, this reaction solution was degassed for 30 minutes under a nitrogen gas atmosphere. Next, the reaction solution was supplied to a jacketed stainless steel double-arm kneader having two sigma-type blades with an openable lid, and the system was replaced with nitrogen gas while the reaction solution was kept at 30°C.
[0207] Next, 0.24 parts by mass of ammonium persulfate and 0.012 parts by mass of L-ascorbic acid were added to the reaction solution while stirring, and polymerization started about 1 minute later. Then, polymerization was carried out at 30° C. or higher and 95° C. or lower, and a hydrogel-like crosslinked polymer was taken out 60 minutes after the start of polymerization.
[0208] The obtained hydrogel was dried with hot air at 150° C. for 100 minutes. Next, the dried product was pulverized using a vibration mill and further classified using JIS standard sieves with mesh sizes of 850 μm and 106 μm to obtain an irregularly pulverized water absorbent resin precursor (1).
[0209] To 200 parts by mass of the obtained water absorbent resin precursor (1), 1800 parts by mass of a 0.9% by mass aqueous sodium chloride solution (physiological saline) was added, and the mixture was allowed to stand at room temperature for 8 hours or more to prepare a simulated used water absorbent resin (1).
[0210] Next, 50 g of the simulated used water absorbent resin (1), 7.50 g of a 15% by mass aqueous sodium carbonate solution as a pH adjuster, and 0.33 g of a 30% by mass aqueous hydrogen peroxide solution as a decomposition agent were added to a reaction vessel to prepare a mixture. The amount of the pH adjuster added was adjusted so that the pH of the mixture was 8.0 to 8.5.
[0211] Next, the decomposition reaction was initiated by immersing the reaction vessel containing the mixture in a thermostatic bath at 80° C. After one hour had passed, the decomposition state of the mixture was checked, and no gel-like matter was confirmed, and almost all of the simulated used water absorbent resin (1) was decomposed and solubilized.
[0212] Next, in order to remove hydrogen peroxide remaining in the aqueous solution, 4.0 g of a 15% by mass aqueous solution of sodium carbonate was added, and the mixture was stirred for 3 hours while maintaining the temperature at 25°C. After that, the amount of hydrogen peroxide remaining in the aqueous solution was measured, and it was confirmed that it was below the detection limit, and almost all of the hydrogen peroxide had been removed. Finally, p-methoxyphenol was added as a polymerization inhibitor at 100 ppm relative to the solid content of the solubilized polymer, and mixed. The solid content concentration of the solubilized polymer (1) aqueous solution thus obtained was 8.1% by mass. In the solubilized polymer (1), L-ascorbic acid was 2 ppm, hydrogen peroxide was 10 ppm, and the amount of transition metal ions was 5 ppm. The YI value in the solubilized polymer (1) was also 8.
[0213] [Reference example 1] Into a reaction vessel, 100.2 g of acrylic acid, 65.0 g of ion-exchanged water, and 0.40 g of polyethylene glycol diacrylate (molecular weight 523) were added and mixed to prepare an aqueous monomer solution (Reference 1').
[0214] Next, the reaction vessel containing the monomer aqueous solution (Reference 1') was immersed in an ice bath, and 83.7 g of a 48.5% by mass aqueous sodium hydroxide solution was added little by little while stirring so that the temperature of the monomer aqueous solution (Reference 1') did not exceed 30°C, to obtain a monomer aqueous solution (Reference 1). Thereafter, the monomer aqueous solution (Reference 1) was subjected to nitrogen gas replacement for 30 minutes.
[0215] Next, the reaction vessel was immersed in a warm water bath at 50°C while stirring the aqueous monomer solution (Reference 1), and when the temperature of the aqueous monomer solution (Reference 1) reached 30°C, 0.178g of sodium persulfate and 0.004g of L-ascorbic acid were added, and polymerization started about 2 minutes later (polymerization induction time). Thereafter, polymerization was continued while immersed in the warm water bath, and the hydrogel (Reference 1) was taken out 60 minutes after the start of polymerization.
[0216] The obtained hydrogel (Reference 1) was crushed with a meat chopper having a die diameter of 7.5 mm, and then dried with hot air at 190° C. for 20 minutes. The dried product was then crushed with a vibration mill, and the crushed product was classified with JIS standard sieves having openings of 850 μm and 150 μm to obtain an irregularly crushed water-absorbent resin precursor (Reference 1).
[0217] 100 parts by mass of the obtained water absorbent resin precursor (Reference 1) was uniformly mixed with a surface crosslinking agent solution consisting of 0.030 parts by mass of ethylene glycol diglycidyl ether, 1.35 parts by mass of propylene glycol, and 3.15 parts by mass of deionized water, and the mixture was subjected to a heat treatment at 100°C for 45 minutes.
[0218] After that, the mixture was cooled and mixed uniformly with an aqueous solution consisting of 1 part by mass of deionized water and 0.01 part by mass of trisodium diethylenetriaminepentaacetate. The mixture was dried at 60°C for 1 hour and then passed through a JIS standard sieve with a mesh size of 710 μm to obtain a water-absorbent resin (Reference 1).
[0219] The obtained water absorbent resin (Reference 1) had a CRC of 36.8 g / g, an AAP0.3 of 26.9 g / g, and a YI value of 13.5.
[0220] [Comparative Example 1] A reaction vessel was charged with 90.2 g of acrylic acid, 80.0 g of ion-exchanged water, 0.36 g of polyethylene glycol diacrylate (molecular weight 523), and 152.1 g of the aqueous solution of solubilized polymer (1) obtained in Production Example 1 (solid concentration: 8.1% by mass, temperature: 25°C) and mixed to obtain an aqueous monomer solution (C1').
[0221] Next, the reaction vessel containing the monomer aqueous solution (C1') was immersed in an ice bath, and 75.3 g of a 48.5 mass% aqueous sodium hydroxide solution was added little by little while stirring so that the temperature of the monomer aqueous solution (C1') did not exceed 30°C, to obtain a monomer aqueous solution (C1). Thereafter, the monomer aqueous solution (C1) was subjected to nitrogen gas replacement for 30 minutes.
[0222] Next, the reaction vessel was immersed in a warm water bath at 50° C. while stirring the aqueous monomer solution (C1), and when the temperature of the aqueous monomer solution (C1) reached 30° C., 0.167 g of sodium persulfate and 0.004 g of L-ascorbic acid were added, and polymerization started about 10 minutes later (induction time of polymerization). Thereafter, polymerization was continued while immersed in the warm water bath, and 60 minutes after the start of polymerization, the hydrogel (C1) was taken out.
[0223] The obtained hydrogel (C1) was crushed with a meat chopper having a die diameter of 7.5 mm, and then dried with hot air at 190° C. for 20 minutes. The dried product was then crushed with a vibration mill, and the crushed product was classified with JIS standard sieves having openings of 850 μm and 150 μm to obtain an irregularly crushed water-absorbent resin precursor (C1).
[0224] 100 parts by mass of the obtained water absorbent resin precursor (C1) was uniformly mixed with a surface crosslinking agent solution consisting of 0.030 parts by mass of ethylene glycol diglycidyl ether, 1.35 parts by mass of propylene glycol, and 3.15 parts by mass of deionized water, and the mixture was subjected to a heat treatment at 100° C. for 45 minutes.
[0225] Then, the mixture was cooled and mixed uniformly with an aqueous solution of 1 part by mass of deionized water and 0.01 part by mass of trisodium diethylenetriaminepentaacetate. The mixture was dried at 60°C for 1 hour and then passed through a JIS standard sieve with a mesh size of 710 μm to obtain a water-absorbent resin (C1).
[0226] The obtained water absorbent resin (C1) had a CRC of 36.1 g / g, an AAP0.3 of 25.3 g / g, and a YI value of 15.3.
[0227] [Example 1] A water absorbent resin (1) was obtained by carrying out the same operation as in Comparative Example 1, except that a heated aqueous solution of solubilized polymer (1) (temperature: 60°C) was used instead of the aqueous solution of solubilized polymer (1) at room temperature (25°C) in Comparative Example 1. In Example 1, the induction time until the polymerization time was 2 minutes, which was shorter than the induction time (10 minutes) in Comparative Example 1.
[0228] The obtained water absorbent resin (1) had a CRC of 36.9 g / g, an AAP0.3 of 26.5 g / g, and a YI value of 13.8.
[0229] [Reference example 2] A reaction vessel was charged with 244.9 g of acrylic acid, 0.71 g (0.040 mol % relative to the carboxyl group-containing unsaturated monomer) of polyethylene glycol diacrylate (molecular weight 523) as an internal crosslinking agent, 1.83 g of a 1.0 mass % aqueous solution of trisodium diethylenetriaminepentaacetate (DTPA·3Na), 103.7 g of a 48.5 mass % aqueous solution of sodium hydroxide, and 389.0 g of deionized water, and mixed to prepare an aqueous monomer solution (Reference 2').
[0230] Next, the monomer aqueous solution (Reference 2') was cooled with stirring. When the liquid temperature reached 40.0°C, 100.9 g of a 48.5% by mass aqueous sodium hydroxide solution adjusted to 40°C was added and mixed to obtain a monomer aqueous solution (Reference 2). At this time, the temperature of the monomer aqueous solution (Reference 2) rose to 77.9°C due to the heat of neutralization in the second stage immediately after preparation. Immediately after starting to mix the 48.5% by mass aqueous sodium hydroxide solution, precipitates were observed, but they gradually dissolved and became a transparent homogeneous solution.
[0231] Next, 12.1 g of a 4.0% by mass aqueous solution of sodium persulfate was added to the stirred aqueous solution of monomer (Reference 2), and the mixture was immediately poured into a stainless steel bat-shaped container (bottom surface 340×340 mm, height 25 mm, inner surface; Teflon (registered trademark) coating) in an open-air system. The bat-shaped container was heated using a hot plate until the surface temperature reached 40° C. The time from the start of the second stage neutralization to the pouring of the aqueous monomer solution (Reference 2) into the bat-shaped container was 55 seconds, and the polymerization reaction started 70 seconds (induction time of polymerization) after the aqueous monomer solution (Reference 2) was poured into the bat-shaped container. The polymerization reaction proceeded by expanding and foaming in all directions while generating water vapor, and then contracted to a size slightly larger than that of the bat-shaped container. The hydrogel (Reference 2) was taken out 3 minutes after the start of the polymerization reaction. The series of operations was carried out in an open-air system.
[0232] The hydrogel (Reference 2) obtained by the above polymerization reaction was cut into strips and crushed with a meat chopper with a die diameter of 7.5 mm, after which the hydrogel (Reference 2) was spread on a 50-mesh wire screen and dried with hot air at 190°C for 60 minutes. Next, the gel was crushed with a vibration mill and further classified with JIS standard sieves with mesh openings of 850 μm and 150 μm to obtain an irregularly crushed water-absorbent resin precursor (Reference 2).
[0233] 100 parts by mass of the obtained water absorbent resin precursor (Reference 2) was uniformly mixed with a surface crosslinking agent solution consisting of 0.030 parts by mass of ethylene glycol diglycidyl ether, 1.35 parts by mass of propylene glycol, and 3.15 parts by mass of deionized water, and the mixture was subjected to a heat treatment at 100° C. for 45 minutes.
[0234] Thereafter, the mixture was cooled and passed through a JIS standard sieve with a mesh size of 710 μm to obtain a water-absorbent resin (Reference 2).
[0235] The obtained water absorbent resin (Reference 2) had a CRC of 36.0 g / g, an AAP0.3 of 27.4 g / g, and a YI value of 11.3.
[0236] [Comparative Example 2] A reaction vessel was charged with 220.4 g of acrylic acid, 0.64 g (0.040 mol % relative to the carboxyl group-containing unsaturated monomer) of polyethylene glycol diacrylate (molecular weight 523) as an internal crosslinking agent, 333.3 g of the aqueous solution of solubilized polymer (1) obtained in Production Example 1 (solid content concentration: 8.1 mass %, temperature: 25° C.), 1.83 g of a 1.0 mass % aqueous solution of trisodium diethylenetriaminepentaacetate (DTPA·3Na), 93.4 g of a 48.5 mass % aqueous solution of sodium hydroxide, and 389.0 g of deionized water, and the mixture was mixed to prepare an aqueous monomer solution (C2').
[0237] Next, the monomer aqueous solution (C2') was cooled while stirring. When the liquid temperature reached 40.0°C, 90.8 g of a 48.5% by mass aqueous sodium hydroxide solution adjusted to 40°C was added and mixed to obtain a monomer aqueous solution (C2). At this time, the temperature of the monomer aqueous solution (C2) rose to 77.9°C due to the heat of neutralization in the second stage immediately after preparation. Immediately after starting to mix the 48.5% by mass aqueous sodium hydroxide solution, precipitates were observed, but they gradually dissolved and became a transparent homogeneous solution.
[0238] Next, 10.9 g of a 4.0% by mass aqueous solution of sodium persulfate was added to the stirred monomer aqueous solution (C2), and the mixture was immediately poured into a stainless steel bat-shaped container in an open-air system. The bat-shaped container was heated using a hot plate until the surface temperature reached 40°C. The time from the start of the second stage neutralization to pouring the monomer aqueous solution (C2) into the bat-shaped container was 55 seconds, and the polymerization reaction started 80 seconds (induction time of polymerization) after the monomer aqueous solution (C2) was poured into the bat-shaped container. The polymerization reaction proceeded by expanding and foaming in all directions while generating steam, and then contracted to a size slightly larger than the bat-shaped container. The hydrogel (C2) was taken out 3 minutes after the start of the polymerization reaction. The series of operations was carried out in an open-air system.
[0239] The hydrogel (C2) obtained by the polymerization reaction was cut into strips and crushed with a meat chopper having a die diameter of 7.5 mm, and then the hydrogel (C2) was spread on a 50-mesh wire net and dried with hot air at 190° C. for 60 minutes. The hydrogel was then crushed with a vibration mill and further classified with JIS standard sieves having openings of 850 μm and 150 μm to obtain an irregularly crushed water-absorbent resin precursor (C2).
[0240] 100 parts by mass of the obtained water absorbent resin precursor (C2) was uniformly mixed with a surface crosslinking agent solution consisting of 0.030 parts by mass of ethylene glycol diglycidyl ether, 1.35 parts by mass of propylene glycol, and 3.15 parts by mass of deionized water, and the mixture was subjected to a heat treatment at 100° C. for 45 minutes.
[0241] Thereafter, the mixture was cooled and passed through a JIS standard sieve with a mesh size of 710 μm to obtain a water-absorbent resin (C2). The obtained water-absorbent resin (C2) had a CRC of 36.4 g / g, an AAP0.3 of 26.2 g / g, and a YI value of 13.2.
[0242] [Example 2] A water absorbent resin (2) was obtained by carrying out the same operation as in Comparative Example 2, except that a heated aqueous solution of solubilized polymer (1) (temperature: 60°C) was used instead of the aqueous solution of solubilized polymer (1) at room temperature (25°C), and the raw materials of the water absorbent resin other than the aqueous solution of solubilized polymer (1) (acrylic acid, polyethylene glycol diacrylate, aqueous solution of diethylenetriamine pentaacetate·trisodium (DTPA·3Na), aqueous solution of sodium hydroxide, and deionized water) were preheated to 40°C. In Example 2, the polymerization reaction started 70 seconds (induction time of polymerization) after the aqueous monomer solution was poured into the vat-shaped container.
[0243] The obtained water absorbent resin (2) had a CRC of 36.1 g / g, an AAP0.3 of 27.8 g / g, and a YI value of 11.9.
[0244] [Table 1]
[0245] (summary) Comparing with Examples 1 and 2 (heated mixing) and Comparative Examples 1 and 2 (room temperature mixing), it was confirmed that the use of heated solubilized polymers can suppress the delay in the polymerization induction time. It was also confirmed that the decrease in water absorption properties (AAP0.3) and the increase in coloring can be suppressed.
[0246] [Reference example 3] As a manufacturing apparatus for polyacrylic acid (salt)-based water-absorbing resin, a manufacturing apparatus was prepared which is composed of a solubilized polymer preparation process, a monomer aqueous solution preparation process, a polymerization process, a gel crushing process, a drying process, a crushing process, a classification process, a surface cross-linking process, a cooling process, a granulation process, and a transport process connecting each process. Using the manufacturing apparatus, a polyacrylic acid (salt)-based water-absorbing resin was manufactured.
[0247] First, a monomer aqueous solution (Reference 3) was prepared consisting of 212.4 parts by mass of acrylic acid, 98.9 parts by mass of a 48.5% by mass aqueous sodium hydroxide solution, 1.38 parts by mass of polyethylene glycol diacrylate (molecular weight 523), 2.0 parts by mass of a 1% by mass aqueous solution of pentasodium ethylenediaminetetra(methylenephosphonic acid), and 341.3 parts by mass of deionized water.
[0248] Next, the above-mentioned monomer aqueous solution (Reference 3) adjusted to 40°C was continuously fed by a metering pump, and then 96.1 parts by mass of a 48.5% by mass aqueous sodium hydroxide solution was continuously line mixed. At this time, the liquid temperature of the monomer aqueous solution (Reference 3) rose to 85°C due to the heat of neutralization.
[0249] Furthermore, 11.6 parts by mass of a 4% by mass aqueous solution of sodium persulfate was continuously line mixed and then continuously fed to a continuous polymerization machine having a flat polymerization belt equipped with weirs at both ends so that the thickness was about 7.5 mm. The time from when the aqueous sodium persulfate solution was added until the aqueous monomer solution on the polymerization belt began to expand and foam was recorded as the polymerization initiation time. Polymerization continued thereafter, and a band-shaped hydrogel (Reference 3) was obtained.
[0250] Subsequently, the belt-shaped hydrogel (Reference 3) was cut continuously at equal intervals in the width direction relative to the traveling direction of the polymerization belt, and the cut hydrogel (Reference 3) was chopped into pieces of several mm using a meat chopper, and then spread on a punching metal and dried at 180°C for 30 minutes.
[0251] Next, the entire amount of the dried polymer (Reference 3) at about 60°C obtained in the drying step was pulverized by a roll mill (pulverization step), and then further classified by JIS standard sieves with mesh sizes of 850 μm and 150 μm to obtain a water absorbent resin precursor (Reference 3) in an irregularly pulverized state. In Reference Example 3, the water absorbent resin precursor (Reference 3) was used as a water absorbent resin (Reference 3).
[0252] The above procedure was repeated 10 times, and the average values and fluctuations of the polymerization initiation time and CRC were confirmed. The results are shown in Table 2.
[0253] [Comparative Example 3] Using the same production apparatus as in Reference Example 3, a polyacrylic acid (salt)-based water-absorbing resin was produced.
[0254] First, a monomer aqueous solution (C3) was prepared, which consisted of 193.3 parts by mass of acrylic acid, 81.9 parts by mass of a 48.5% by mass aqueous solution of sodium hydroxide, 1.26 parts by mass of polyethylene glycol diacrylate (molecular weight 523), 1.8 parts by mass of a 1% by mass aqueous solution of pentasodium ethylenediaminetetra(methylenephosphonic acid), 11.4 parts by mass of deionized water, and 296.3 parts by mass of the solubilized polymer (1) aqueous solution (solid content concentration: 8.1% by mass, temperature: 25°C) obtained in Production Example 1. At this time, in the preparation of the monomer aqueous solution of Reference Example 3, the solubilized polymer (1) aqueous solution was continuously added to the monomer aqueous solution (C'3) containing components other than the solubilized polymer (1) aqueous solution in the Venturi tube 40 (Fig. 3) in Fig. 1.
[0255] Next, the monomer aqueous solution (C3) adjusted to 40° C. was continuously fed by a metering pump, and then 79.6 parts by mass of a 48.5% by mass aqueous sodium hydroxide solution was continuously line mixed. At this time, the liquid temperature of the monomer aqueous solution (C3) rose to 85° C. due to heat of neutralization.
[0256] Furthermore, 9.6 parts by mass of a 4% by mass aqueous solution of sodium persulfate was continuously line mixed, and then continuously fed to a continuous polymerization machine having a flat polymerization belt equipped with weirs at both ends so that the thickness was about 7.5 mm. The time from when the aqueous solution of sodium persulfate was added until the aqueous monomer solution on the polymerization belt began to expand and foam was recorded as the polymerization initiation time (induction time). After that, polymerization was continuously performed to obtain a band-shaped hydrogel (C3).
[0257] Subsequently, the belt-shaped hydrogel (C3) was cut continuously at equal intervals in the width direction relative to the traveling direction of the polymerization belt, and the cut hydrogel (C3) was chopped into pieces of several mm using a meat chopper, and then spread on a punching metal and dried at 180°C for 30 minutes.
[0258] Next, the entire amount of the dried polymer (C3) at about 60°C obtained in the drying step was pulverized by a roll mill (pulverization step), and then further classified by JIS standard sieves with mesh sizes of 850 μm and 150 μm to obtain an irregularly pulverized water absorbent resin precursor (C3). In addition, in Comparative Example 3, the water absorbent resin precursor (C3) was used as the water absorbent resin (C3).
[0259] The above procedure was repeated 10 times, and the average values and fluctuations of the polymerization initiation time (induction time) and CRC were confirmed. The results are shown in Table 2.
[0260] [Example 3] A water absorbent resin (3) was obtained by carrying out the same operation as in Comparative Example 3, except that a heated (60°C) aqueous solution of solubilized polymer (1) (temperature: 60°C) was continuously added to the aqueous monomer solution in the Venturi tube instead of the aqueous solution of solubilized polymer (1) at room temperature (25°C). The solubilized polymer (1) used in Example 3 was stored in the storage tank 20 shown in Figure 1 within a range of 60°C ± 5°C for an average residence time of 3 hours.
[0261] The above procedure was repeated 10 times, and the average values and fluctuations of the polymerization initiation time (induction time) and CRC were confirmed. The results are shown in Table 2.
[0262] [Table 2]
[0263] (summary) It can be seen that the use of a heated aqueous solution of solubilized polymer in the addition of an aqueous solution of solubilized polymer (1) to an aqueous monomer solution in continuous polymerization stabilizes the polymerization and physical properties. With the aqueous solution of solubilized polymer at room temperature (25°C), non-uniform mixing, a delay in the polymerization start time and an increase in the range of fluctuation, and an increase in the range of fluctuation in CRC were observed. The mixed state of the above solubilized polymer was confirmed visually by preparing an aqueous solution of solubilized polymer by adding 1% by mass of Blue No. 1 to the aqueous solution of solubilized polymer. [Explanation of symbols]
[0264] 10 Solubilization reaction vessel, 20 storage tanks, 30 Monomer mixing device, 40 Venturi tube, 41 Reduction section, 42 throttle section, 43 Enlarged section, 50 Polymerization equipment, 60 Gel crusher, 70 Drying equipment.
Claims
1. A method for producing a water-absorbent resin, comprising: a polymerization step of polymerizing an unsaturated monomer-containing aqueous solution to obtain a hydrogel-like crosslinked polymer; and a drying step of drying the hydrogel-like crosslinked polymer, the method using a solubilized polymer of a recovered water-absorbent resin as a part of a raw material, A method for producing a water-absorbing resin, wherein the solubilizing polymer is mixed in a heated state at any one of the production steps.
2. The method according to claim 1 , wherein the recovered water-absorbent resin is a used water-absorbent resin recovered from a used absorbent article.
3. The method according to claim 1 or 2, wherein the heated solubilized polymer is heated to a temperature of 30° C. or higher and 100° C. or lower.
4. The method according to claim 1 or 2, wherein the temperature of the heated solubilized polymer is controlled within a range of ±10°C.
5. The method according to claim 1 or 2, wherein the concentration of the solubilized polymer in the heated state is 5% by mass or more in the aqueous solution.
6. The method according to claim 1 or 2, wherein the heated solubilized polymer is mixed in a production step prior to the drying step.
7. The method according to claim 6, wherein the heated solubilized polymer is mixed with the unsaturated monomer and / or the hydrogel-like crosslinked polymer.
8. The process of claim 7, wherein the heated solubilized polymer is mixed with the unsaturated monomer.
9. The method according to claim 8 , wherein the time from adding the polymerization initiator after the mixing to initiating the polymerization is within 5 minutes.
10. The method according to claim 1 or 2, wherein a temperature difference between the solubilizing polymer and the water-absorbent resin raw material to be mixed with the solubilizing polymer is 50° C. or less.
11. The method according to claim 1 or 2, wherein the water-absorbent resin raw material is in a heated state to be mixed with the solubilizing polymer.
12. The method according to claim 1 or 2, wherein the solubilized polymer and the unsaturated monomer-containing aqueous solution are continuously supplied to a pipe, and the solubilized polymer and the unsaturated monomer-containing aqueous solution are mixed in the pipe.
13. 3. The method according to claim 1, wherein the solubilized polymer obtained after the decomposition treatment of the recovered water-absorbent resin is stored in a heated state.
14. 3. The method according to claim 1, wherein the decomposition treatment of the recovered water absorbent resin is carried out with an oxidizing agent.
15. The method of claim 1 or 2, wherein the solubilizing polymer comprises a polymerization inhibitor.
16. The method according to claim 1 or 2, wherein the solubilized polymer has a YI value of 10 or less in an aqueous solution state of 8% by mass or more and 10% by mass or less.
17. The method according to claim 1 or 2, wherein the transition metal ion content in the solubilized polymer is 10 ppm or less (based on the solid content).
18. 3. The method according to claim 1, wherein the L-ascorbic acid content in the solubilized polymer is 10 ppm or less (based on the solid content).
19. The method according to claim 1 or 2, wherein the oxidizing agent in the solubilized polymer is 100 ppm or less (based on solid content).
20. The method according to claim 1 or 2, wherein the heated solubilized polymer is mixed in the production step after filtration.
Citation Information
Patent Citations
Regeneration method for water absorbing resin, and water absorbent
JP2003326161A
Method for producing water-absorbing resin particles
WO2020213298A1
Method for producing water-absorbing resin particles
WO2022080342A1